Hadj Slimane Chérif (Ministre délégué à la Recherche, à la Technologie et à l'Environnement) - Blin, Louis; Abdi, Noureddine; Redjala, Ramdane; Stora, Benjamin (Algérie: 200 hommes de pouvoir, 1992)

Chikh Slimane (ex-ministre de l'Education) - Blin, Louis; Abdi, Noureddine; Redjala, Ramdane; Stora, Benjamin (Algérie: 200 hommes de pouvoir, 1992)

The Transition form slavery, 1873-1914 - Sheriff, Abdul; Ferguson, Ed (Zanzibar under colonial rule, 1991)
Don John C. Wilkinson (mars 2026)

De Ben Gardan à Tripoli - Monmarché, Marcel (Algérie [et] Tunisie: Tripolitaine, Malte, 1930)

De Gabès à Djerba - Monmarché, Marcel (Algérie [et] Tunisie: Tripolitaine, Malte, 1930)

Mūnis al-Aḥibba fī Ahbār Ǧirba - Abdesselem, Ahmed (Les historiens tunisiens des XVIIe, XVIIIe et XIXe siècles: essai d'histoire culturelle, 1973)
Keywords: Djerba – Empire ottoman; Famille Bin Jlūd; Jumni; Abu Ishaq Ibrahim al-; Malikisme – Djerba; Muʻaskarī; Muḥammad ibn Aḥmad al-; 1737-1823; Récits de voyage – Djerba; Vie intellectuelle – Tunisie

La conquista di Tripoli nel 1510 vista della Sicilia - Traselli, Carmelo (Mélanges en l'honneur de Fernand Braudel. 1, Histoire économique du monde méditerranéen, 1450-1650, 1973)
Keywords: Famille Samūmnī; Relations – Djerba – Sicile

اسماعیل السني - أحمد إبن أبي الضياف (إتحاف أهل الزمان بأخبار ملوك تونس و عهد الأمان, 1989)
Keywords: Biographies

أبو بكر صدام - إبن أبي الضياف, أحمد (إتحاف أهل الزمان بأخبار ملوك تونس و عهد الأمان, 1989)
Keywords: Biographies

صالح شیبوب - إبن أبي الضياف, أحمد (إتحاف أهل الزمان بأخبار ملوك تونس و عهد الأمان, 1989)
Keywords: Biographies

عبد الرحمان بن عياد - إبن أبي الضياف, أحمد (إتحاف أهل الزمان بأخبار ملوك تونس و عهد الأمان, 1989)
Keywords: Biographies

محمد المعيلل - إبن أبي الضياف, أحمد (إتحاف أهل الزمان بأخبار ملوك تونس و عهد الأمان, 1989)
أبو عبد الله محمد ابن الحاج عمد العيلل التميمبي القيرواني من أعيان قبائل الفعح بالقيروان » نشا في طلب العلم ء وأخذ عن أعيان العلماء بالقيروان » كالفقيه الحاج قاسم بو الاجفان › والشيخ القاضي أبي عبد الله عمد بوراس وغيرهما وتصدر للتدريس والتوثيق ‏ ثم ولي القضاء ببلاده » ثم التقل للفتوى . وكان حيرا » فقيها عفيفا » موتا . ولم يزل على حاله » متجملا بخلاله » الى ان توفي سنة 1275 خحمسين وسبعين ومائتين والف (1858/59 م)
Keywords: Biographies

محمد بن حميدة بن عیاد - إبن أبي الضياف, أحمد (إتحاف أهل الزمان بأخبار ملوك تونس و عهد الأمان, 1989)
Keywords: Biographies

محمد بوراس - إبن أبي الضياف, أحمد (إتحاف أهل الزمان بأخبار ملوك تونس و عهد الأمان, 1989)
أبو عبد الله حمد ابن الاج احمد بوراس الهذل القيرواف . نشا في طلب العلم » ناسجا على منوال آله › في غالب أحواله . وأخذ عن الشيخ أبي بكر صدام » وأبي محمد حمودة الوحيشي › وأبي عبد الله محمد بن عبد الغرياني » وغيرهم من علماء القيروان . وحصل العلم » وتصدر للتدريس > واختار ما يبقى بعد الموت من الاعمال › وهو بث العلم ي صدور الرجال . وكان عالا صاعلا » تقيا فقيها » عدا فاضلا وجيها . وتوي ي رجب من سنة 1250 خحمسين ومائتين والف (نوفمبر 1834 م.) .
Keywords: Biographies

يوسف امير عسكر زواوة - إبن أبي الضياف, أحمد (إتحاف أهل الزمان بأخبار ملوك تونس و عهد الأمان, 1989)
Keywords: Biographies

Les réseaux marchands arabes et swahili en Afrique orientale - Kagabo, Jose (Marchands et hommes d'affaires asiatiques: dans l'océan Indien et la mer de Chine 13e-20e siècles, 1988)
Keywords: Commerce – Oman; Commerce – Zanzibar – 19e siècle; Tippo Tip (1837-1905)

Les Berbères kutāma dans les stratégies de pouvoir - Souidi, Djamel (Les assises du pouvoir: temps médiévaux, territoires africains, 1994)

دور جزيرة جربة الإقتصادي بين القرنين الخامس والتاسع هـ - حسن, محمد (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Commerce – Djerba

Projet de ceinture verte - Marrakchi, Abdulwahab (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie – Djerba; Littoraux – Djerba

Approche explicative de l'évolution morphogénétique du littoral et des ploges à Djerba - Yamoun, Messaoud (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie – Djerba; Littoraux – Djerba

Note sur les activités d’extraction de la pierre et du sable à Djerba - Yamoun, Messaoud (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie – Djerba; Littoraux – Djerba

Formes et évolutions actuelles du littoral de Djerba-Zarzis - Ben Ouezdou, Hedi; Rebhi, Ameur (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie – Djerba; Littoraux – Djerba

Le traditionnalisme judéo-africain: La Ghriba de Djerba et la leçon qui s'en dégage - Absalon, Adon (Annuaire israelite de Tunisie, 1948)
Keywords: Judaïsme – Djerba

التجربة الوقفية العمانية - السيابي, أحمد بن ‏سعود (الحلقة النقاشية حول التجارب الوقفية الدولية, 1997)
Keywords: Waqf (fondations) – Oman

Tunisi - Svezia 23 Dicembre 1736: Trattato di pace e di Commercio (Trattati, convenzioni e accordi relativi all'Africa: 1648-1799, 1940)
Keywords: Commerce – Djerba; Commerce – Zouara; Relations – Tunisie – suède

التشريع والفكر العمراني الاباضي - الشيخ بالحاج, بكير بن يحي (العمارة والعمران الاباضي بوادي ميزاب: ملف حول الأيام الدينية الخامسة المنعقدة بالعالية يومي الخميس والجموعة 5-6 ذي الحجة 1410هـ 28-29 جوان 1990م, 1990)
Keywords: Urbanisme – Mzab

تأثر المدينة بالتحولات العميقة في الميدان الاقتصادى ونتائجه فى الميدان الاجتماعي والعمراني - الشيهاني, باعمور (العمارة والعمران الاباضي بوادي ميزاب: ملف حول الأيام الدينية الخامسة المنعقدة بالعالية يومي الخميس والجموعة 5-6 ذي الحجة 1410هـ 28-29 جوان 1990م, 1990)
Keywords: Urbanisme – Mzab

تاریخ وادي ميزاب - بسيس, قاسم بن سعيد (العمارة والعمران الاباضي بوادي ميزاب: ملف حول الأيام الدينية الخامسة المنعقدة بالعالية يومي الخميس والجموعة 5-6 ذي الحجة 1410هـ 28-29 جوان 1990م, 1990)
Keywords: Urbanisme – Mzab

الازمة الخاصة بالعمارة كمبنى في وادى ميزاب - بغيلي, صالح بن محمد (العمارة والعمران الاباضي بوادي ميزاب: ملف حول الأيام الدينية الخامسة المنعقدة بالعالية يومي الخميس والجموعة 5-6 ذي الحجة 1410هـ 28-29 جوان 1990م, 1990)
Keywords: Urbanisme – Mzab

التواصل أو القطيعة - بكلي, عمر بن محمد (العمارة والعمران الاباضي بوادي ميزاب: ملف حول الأيام الدينية الخامسة المنعقدة بالعالية يومي الخميس والجموعة 5-6 ذي الحجة 1410هـ 28-29 جوان 1990م, 1990)
Keywords: Urbanisme – Mzab

اشكالية الموضوع الفكر العمراني الاباضي - بن يوسف, ابراهيم بن سليمان (العمارة والعمران الاباضي بوادي ميزاب: ملف حول الأيام الدينية الخامسة المنعقدة بالعالية يومي الخميس والجموعة 5-6 ذي الحجة 1410هـ 28-29 جوان 1990م, 1990)
Keywords: Urbanisme – Mzab

حوار حول الهندسة المعمارية ، ووضع اشكاليتها ضمن مشكل انهيار التقاليد الاجتماعية والفنون التقليدية فى وادى ميزاب - تزقغين, سليمان (العمارة والعمران الاباضي بوادي ميزاب: ملف حول الأيام الدينية الخامسة المنعقدة بالعالية يومي الخميس والجموعة 5-6 ذي الحجة 1410هـ 28-29 جوان 1990م, 1990)
Keywords: Urbanisme – Mzab

Les fêtes maraboutiques en Tunisie - Zarda - Ferchiou, Sophie (Actes du premier congrès d'études des cultures méditerranéennes d'influence arabo-berbère, 1973)
Keywords: Croyances populaires – Djerba

Rencontre : Vasco de Gama et Ibn Madjid - Barry, Michael (Sultanat d'Oman: retour à l'histoire, 1998)
Keywords: Relations – Oman – Portugal

Vers demain: impressions de voyage (1997) - Bausset, Philippe de (Sultanat d'Oman: retour à l'histoire, 1998)
Keywords: Récits de voyage – Oman

Politique touristique et protection de l'environnement - Bouagga, Djalel (Sultanat d'Oman: retour à l'histoire, 1998)
Keywords: Tourisme – Oman

De l'antique Mascate au nouvel Oman - Charnay, Jean Paul (Sultanat d'Oman: retour à l'histoire, 1998)

Indépendance et ouverture - Oddos, Robert (Sultanat d'Oman: retour à l'histoire, 1998)

Economie: le second souffle - Salamé-Hardy, Katia (Sultanat d'Oman: retour à l'histoire, 1998)

Hier: encens, marins et forteresses - Thoraval, Yves (Sultanat d'Oman: retour à l'histoire, 1998)
Keywords: Coutumes – Oman

Impressions d'aujourd'hui: dynastie et modernité - Thoraval, Yves (Sultanat d'Oman: retour à l'histoire, 1998)

Names of Aromata in Semitic and Cushitic Languages - Banti, G.; Contini, R. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Il giardino del Dio - Betrò, M. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Perfumes and Power - Bowersock, G. W. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Incenso Mirra e Cinnamomo. Prodotti esotici nella farmacopea egiziana antica - Bresciani, E. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Evidence for the Use of Aromatics in the Early Bronze Age of Oman: Period III at RJ-2 (2300-2200 BC) - Cleuziou, Serge; Tozi, M. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

II ruolo dell'Arabia nel commercio delle spezie e dell'incenso: da Elio Gallo a Vosco da Gama - Costa, Paolo M. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Incense and Perfumes in the Late Bronze Age Aegean - D'agata, A. L. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

The Frankincense Road from Najrân to Ma'ân: a Hypothetical Itinerary - De Maigret, A. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Tus e murra: aromi sudarabici nella Roma arcaica - De Romanis, F. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

L'Egitto tolemaico e la terra degli aromata - Fantasia, U. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

The Contacts between Southern Arabia and the Horn of Africa in Late Prehistoric and Early Historical Times: a View from Africa - Fattovich, R. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

La produzione del balsamo nell 'oasi di Engaddi (Israele). Su alcuni nuovi documenti dal deserto di Giuda - Gnoli, T. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Kingship and Perfumes: Antiochus TV and Alexander the Great - Grottanelli, C. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Coppe e bracieri da incenso nell 'oriente classico - Invernizzi, A. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Beyond Deserts, beyond Oceans - Liverani, M. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Trade Routes and Trade Goods at the Northern End of the «Incense Road» in the first Millennium B.C. - Macdonald, M.C.A. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Complex Society, Urbanization and Trade: the Case of Eastern and Western Arabia - Mazzoni, S. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

The Harvesting of Frankincense in Dhofar, Oman - Morris, Miranda (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Les échanges entre l'Arabie du Sud et la péninsule d'Oman du 3ème siècle av. J.-C. au 4ème siècle ap. J.-C. - Mouton, Michel (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Namen von Aromata im antiken Süd-arabien - Müller, Walter W. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Do Anchors Mean Ships? Underwater Evidence for Maritime Trade along the Dhofar Coast, Southern Indian Ocean - Owen, J. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Al-Hâmid: a Route to the Red Sea? - Phillips, Carl (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

The Arab Connection. Political Implications of Frankincense in Early Greece - Retsö, J. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Arabie Méridionale: l'état et les aromates - Robin, C.J. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Profumo di terra: valori e simboli dell 'immaginario romano - Rosati, G. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Milan: Discovery of Frankincense Lumps in a Roman Burial - Rossignani, M. P. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Deux noms de mesures dans les textes sud-arabes sur bois - Ryckmans, J.; Drewes, A. J. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Dell'uso dell'incenso in epoca romana - Salmeri, G. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Sea-trade of the Hadramawt Kingdom from the 1st to the 6th Centuries A.D. - Sedov, A. V. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Caravans across the Eastern Desert of Egypt: Recent Discoveries on the Berenike-Apollinopolis Magna-Coptos Roads - Sidebotham, S. E. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Profumi e filosofia nell'Atene di Socrate - Soverini, L. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Un modo arcaico di produzione vetraria: viaggio nel tempo al seguito di unafonte contemporanea - Taborelli, L. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

L'incenso e gli incensieri nel mondo greco - Zaccagnino, C. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Notes sur l'Arabie dans les sources classiques - Zambrini, A. (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Mesopotamia and Frankincense: the Early Evidence - Zarins, Juris (Profumi d'Arabia: atti del convegno, 1997)
Keywords: Archéologie – Oman

Islam and Cultural Hegemony: The Ideology of Slaveowners on the East African Coast - Cooper, Frederick (The ideology of slavery in Africa, 1981)
Keywords: Esclavage – Zanzibar

Oman and Yemen : the Southern Fringe - Held, Colbert C. (Middle East patterns: places, peoples, and politics, 1994)

Etnografia delle popolazioni libiche - Agostini, Enrico de (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Italie – colonies

L'importanza dell'elemento ebraico nella popolazione della Tripolitania - Artom, Elia S. (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Judaïsme – Djebel Nefousa

Note al programma per l'explorazione archeologica della Tripolitania - Aurigemma, Salvatore (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Archéologie – Djebel Nefousa

Il movimento demografico della Tripolitania in rapporto allo sviluppo agrario - Battara, Pietro (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Italie – colonies

Gli Studi di linguistica berbera - Beguinot, Francesco (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Linguistique – Djebel Nefousa

Cacce indigene in Tripolitania dall'antichitaà ad oggi - Corò, Francesco (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Italie – colonies

Alcuni recenti studi di lingua e letteratura araba relativi all'Africa settentrionale - Guidi, Michelangelo (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Italie – colonies

La Contestata zona Sud-Occidentale della Tripolitania - Circostanze dell'occupazione francese - Nava, Santi (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Italie – colonies

Saggio d'una pianta etnografica della città di Tripoli di Barberia - Ricci, Ettore (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Italie – colonies

I Risultati scientifici e pratici delle campagne archeologiche coloniali - Romanelli, Pietro (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Archéologie – Djebel Nefousa

Considerazioni generali sulla storia della libia durante il domino degli Arabo-Berberi e dei Turchi - Rossi, Ettore (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Italie – colonies

La poesia popolare araba della Tripolitania - Rossi, Ettore (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Poésie – Djebel Nefousa

Tipi indigeni di insediamento umano e loro distribuzione nella Tripolitania settentrionale - Scarin, Emilio (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Italie – colonies

La S. Sede e i Barbareschi al principio del secolo scorso - Veccia Vaglieri, Laura (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)

Un rapporto del grande ammiraglio Piyale pascia a Solimano sull'assedio delle Gerbe, 1560 - Bombaci, Alessio (Festschrift Friedrich Giese aus Anlass des siebenzigsten Geburtstags überreicht von Freunden und Schülern, 1941)
Keywords: Invasions chrétiennes – Djerba – 1560

La strada romana da Tabunacti a Cydamus : da Nalut a Gadames, Tripolitania occidentale - Corò, Francesco (Atti del primo Congresso di studi coloniali: Firenze 8-12 aprile 1931, 1931)

Ieffren - Asabaa - Garian - Tarhuna - Cortese, Emilio (Atti del IX Congresso Geografico Italiano tenuto in Genova dal 22 al 30 Aprile 1924, 1925)

Vernacular Architecture - Hutt, Antony; Petherbridge, Guy T. (Islamic art and architecture in Libya, 1976)
Keywords: Architecture – Djebel Nefousa

الوضيفة التربوية للأسرة بين الأمس واليوم - بوصباع, إبراهيم (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

دور الأمومة في نقل القيم إلى الأحيال القادمة - بكلي, عائشة (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

الأسرة المحلية بين قيم المجتمع التقليدي وقيم المجتمع الحديث - حجاج, قاسم بن حمو; بكلي, عزيزة (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

ملامح الأسرة المنشودة - باحريز, عائشة; بابكر, عزيزة (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

الظواهر الاجتماعية السلبية: أسبابها وحلولها - الحاج سعيد, بكير بن حمودة; بكوش, صالح (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

الطلق: الأسباب والحلول - باحريز, صفية; بابكر, سمية (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

قانون الأسرة بين الرفض والقبول - بويزري, سعيد; بكوش, محمد بن موسى (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

المرأة المسلمة الحقوق والواجبات - بوحديبة, بية; مرامرية, فاطمة (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

واقع الأسرة المحلية المغتربة في مدن الشمال والجنوب وخارج الوطن - بحاز, إبراهيم بن بكير; الشيخ بالحاج, بكير بن محمد; أبو بكر, صالح بن عبد الله (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

الأسرة المحلية ظواهر ومؤشرات - بابكر, محمد; فخار, حنان (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

التحول الاقتصادي وآثره على التحويل الأسري والمجتمع - دجال, محمد; تزبينت, سعيد (كتيب المحاضرات والندوات: الأسرة المحلية وتحديات التحديث من أجل بناء أسرة نستقرة أصيلة ومعاصرة. الأيام الثقافية السادسة من 14 إلى 22 ربيع الثاني 1419هـ الموافق لـ 7 إلى 14 اوت 1998م, 1998)

Annexe de Djerba - Lecore-Carpentier, Edmond (L'Indicateur tunisien : annuaire des administrations de la Régence de Tunis guide du commerce, de l'industrie, de l'agriculture et des touristes, 1906)
Keywords: Agriculture – Djerba – 1881-1956; Artisanat – Djerba; Commerce – Djerba – 1881-1956; Judaïsme – Djerba; Pêche – Djerba

‏قصيدة ‏ضياء الدين أنعيم من الضياء - دواق, سليمان بن عمر (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)
Keywords: Poésie – Mzab

‏القضاء عند الشيخ عبد العزيز الثميني - بحاز, إبراهيم بن بكير (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)

‏الشيخ عبد العزيز الثميني وصلته بعمان - بوحجام, محمد بن قاسم ناصر (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)

‏محاضرة حول تفسيره قصيدة الشيخ عبد العزيز بن إبراهيم الثميني - بوناطيرو, لوط (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)
Keywords: Poésie – Mzab

‏القاعدة اصل الإباضية - القنواتي, مروان (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)

‏منهج ‏الاختصار عند الثميني من كتاب ابي مسألة والألواح - صدقي, محمد بن ايوب (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)

‏المنطق وعلم الكلام يا عم ضياء الدين عبد العزيز الثميني - سعيد, عليوان (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)

الثميني ‏من خلال كتاب الأفعال المنهجيه من المهلكة - طلاي, إبراهيم بن محمد (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)

‏إعتناء الشيخ عبد العزيز الثميني رحمه الله بتعليم الحساب - زروقي, عبد المقتدر (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)
Keywords: Mathématiques – Mzab

‏مكانة الإمام الثميني في علم الكلام - ميمون, الربيع (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)

‏ضياء الدين عبد العزيز الثميني من خلال كتابات بخط يده وبعض مخطوطات نادرة - إسماعيل, عمر (محاضرات الأيام الدراسية حول فكر ضياء الدين الشيخ عبد العزيز الثميني, 1999)

Juifs de mémoire - Brenner, Frédéric (Mémoire et histoire: données et débats: actes du XXVe Colloque des intellectuels juifs de langue française, 1986)
Keywords: Judaïsme – Djerba

Abdullah al-Salimi's Role in the Ibadi Revivial (1913-20) - Ubaydli, Ahmad (Proceedings of the 1988 international conference on Middle Eastern studies held at the university of Leeds between 10-13 July 1988, 1988)
Keywords: Vie politique – Oman – 1913-1932

The Typology of Omani Arabic Dialects - Holes, Clive (Proceedings of the 1988 international conference on Middle Eastern studies held at the university of Leeds between 10-13 July 1988, 1988)
Keywords: Linguistique – Oman

Acte notarié de location d'une pêcherie des environs d'Adjim à Djerba en date du 19 septembre 1895 (Affaire du plateau continental Tunisie-Jamahiriya arabe libyenne : mémoire du gouvernement de la République tunisienne, 1981)
Keywords: Actes notariés – Djerba; Pêche – Djerba

Problème verbal dans le parler berbère de Siwa - Basset, André (Mélanges Maspéro. III - Orient islamique, 1935)
Keywords: Linguistique – Siwa

Abou Yazid, l'anarchiste licencieux d'envergure exceptionnelle - Bouali, Mahmoud (La sédition permanente en Tunisie, 1972)
Keywords: Ibn Kaydad

De l'exutoire italique à la révolte d'Abou Yazid - Bouali, Mahmoud (La sédition permanente en Tunisie, 1972)
Keywords: Ibn Kaydad

Parure, apprentissage et initiation - Harzallah, Féthia; Lambert, Jean (Noces tissées, noces brodées: parures et costumes féminins de Tunisie: exposition, 29 mars- 3 juillet 1995, 1995)
Sur la Hejba
Keywords: Moeurs et coutumes – Djerba

Maquillage et soins du corps - Ben Tanfous, Aziza (Noces tissées, noces brodées: parures et costumes féminins de Tunisie: exposition, 29 mars- 3 juillet 1995, 1995)
Keywords: Artisanat – Djerba

Le langage des femmes tunisiennes - Saada, Lucienne (Mélanges Marcel Cohen: études de linguistique, ethnographie et sciences connexes offertes par ses amis et ses élèves à l'occasion de son 80ème anniversaire, 1970)
Keywords: Linguistique

L'Afrique du Nord - Bernard, Augustin (L'habitation indigène dans les possessions françaises, 1931)
Keywords: France – Colonies

Siwa et Aoudjila, problème verbal berbère - Basset, André (Mélanges Gaudefroy-Demombynes : Mélanges offerts à Gaudefroy-Demonbynes par ses amis et anciens élèves, 1945)
Keywords: Linguistique

Planteurs et marchands arabes omani en Afrique orientale et centrale au XIXe siècle - Le Cour Grandmaison, Colette (Compte-rendu de la Réunion des chercheurs sur le monde arabe et musulman, Aix-en-Provence, 30 juin, ler & 2 juilet 1986, 1986)
Keywords: Relations – Oman – Congo

La cité ibadite: urbanisme et vie sociale au XIe siècle d'après un document inédit : d'Abū 'l-Abbas Ahmad, le Kitab Uṣūl al-Araḍīn - Cuperly, Pierre (Compte-rendu de la Réunion des chercheurs sur le monde arabe et musulman, Aix-en-Provence, 30 juin, 1er & 2 juillet 1986, 1986)
Keywords: Urbanisme – Mzab

Document de synthèse du séminaire approuvé par l'Assemblée plénière - Assidje (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Réflexions sur la sauvegarde du patrimoine et la protection du site à Djerba - El Bahi, Mohamed (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Oman and the Trade Routes across the Indian Ocean in Islamic Times - Salim, Sahar Assayed Abdul-Aziz (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)

An Inscription in Memory of Sayyid bin Abu 'Ali - a study of the Relationship between China and Oman from the 11th-15th Centuries - Yingsheng, Liu (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)
Keywords: Relations – Oman – Chine

Sohar and the Maritime Silk-Road - Kervran, Monique (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)

Archaeological Evidence of Overseas Contacts between Omani Traders and the Far East and the Outer World prior to the opening of the Cape Route - Costa, Paolo M. (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)
Keywords: Archéologie – Oman

Oman's Role in the Maritime Silk Route: Human, Commercial and Navigational Factors towards a Maritime Achievement - Severin, Timothy (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)
Keywords: Navigation – Oman

The Indus Civilization and its Inter-relation with Oman in Maritime Perspective - Dani, Ahmad Hasan (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)
Keywords: Relations – Oman – Inde

The Influence of Trade Routes Relating to Oman in Ancient Times - Rayah, A.S. al- (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)

Prehistoric Origins of Seafaring a long t he Oman Coast - Cleuziou, Serge (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)
Keywords: Archéologie – Oman

The Contribution of Oman to the Cultural Links between Nations - Allawati, Malallah bin Ali bin Habib (The United Nations Educational Scientific and Cultural Organization (UNESCO) Project to study the Silk Routes : Papers submitted at the International Seminar on the Silk Roads held at Sultan Qaboos University, Muscat, Sultanate of Oman, 20-21 November 1990, 1992)
Keywords: Oman – Histoire

توثيق المصادر العمانية - Pearson, J. (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Sources – Oman

الاتفاقات الدولية مع سلطنة عمان - Bidwell, Robin (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Politique étrangère – Oman

الأفلاج العمانية ومجاري المياه - Utroy, Francisco (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Irrigation – Oman

نشأة الأفلاج في عمان - Wilkinson, John Craven (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Irrigation – Oman

دراسة تمهيدية عن النقوش الاسلامية في صلالة بالمنطقة الجنوبية - Oman, Giovanni (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

صناعة الهك و صور لبعض الصنعات (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Artisanat – Oman

صناعة الفخار و صور لبعض الصنعات (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Artisanat – Oman

صناعة من سعف النخيل و صور لبعض الصنعات (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Artisanat – Oman

صناعة الحصر و السلام و صور لبعض الصنعات (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Artisanat – Oman

صناعة الجلود و صور لبعض الصنعات (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Artisanat – Oman

الصناعة المعدنية (النحاسية) و صور لبعض المصنوعات (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Artisanat – Oman

الصناعة المعدنية (الفضية) و صور لبعض المصنوعات (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Artisanat – Oman

صناعة الغزل والنسيج وصور لبعض المنسوجات (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Artisanat – Oman

السفن ونماذج منها (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Artisanat – Oman

دور العرب والفرس في مكافحة الاستعمار البرتغالي في الخليج (دراسة مقارنة) - العقاد, صلاح (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Relations – Oman – Portugal

صفحات مطوية من تأثيات الحضارة العمانية في المغرب - أيوب, محمد سليمان (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

اباضية عمان ونشر الاسلام في بلاد المغرب - كاشف, سيدة إسماعيل (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

الصلات التاريخية بين المغرب وعمان - التازي, عبد الهادي (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Relations – Oman – Afrique du Nord

دور عمان في بناء حضارة شرقي افريقية - الشيخ, رأفت غنيمي (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

الدولة العمانية قي شرق افريقية - قاسم, جمال زكريا (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

دور عمان في نشاط التجارة العالمية في العصر الاسلامي الأول - الجنحاني, الحبيب (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

الأفلاج العمانية ونظامها - العبري, بدر بن سالم (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Irrigation – Oman

دور عمان في نشر الاسلام في شبه القارة الهندية - المسعودي, مير ولي خان (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Relations – Oman – Inde

الحضارة الاسلامية ودور العمانيين في تطويرها - شلبي, أحمد (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

الاستحكامات الحربية في مسقط - ماهر, سعاد (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

الدولة العمانية : نشأتها وازدهارها - عبدواني, صادق حسن (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

دولة اليحمد في عمان - الخروصي, سليمان (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

عمان حصن الأمان للعروبة والإسلام - عاشور, سعيد عبد الفتاح (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

أرض اللبان في سلطنة عمان - الغساني, عبد القادر (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

دور عمان الحضاري في فجر التاريخ - الناضوري, رشيد (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

عمان في التاريخ: من أقدم العصور حتى الآن - شلبي, أحمد (حصاد ندوة الدراسات العمانية البحوث والدراسات التي قدمت في الندوة ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

Three problems in conservation: Egypt, Oman and Yemen - Lewcock, Ronald (Conservation as Cultural Survival, 1980)
Keywords: Monuments – Oman

La technologie de la teinture traditionnelle au kermès en Tunisie - Oueslati, Issam; Ayed, Naceur (Between the Natural and the Artificial. Dyestuffs and Medicines, 1999)
Keywords: Artisanat – Djerba

Les synagogues de Tunisie: recherches architecturales - Saadaoui, Ahmed (Histoire communautaire, histoire plurielle: la communauté juive de Tunisie, 1999)
Keywords: Judaïsme – Djerba

ملاحظات في إحياء ذكرى سعيد بن أبو علي دراسة حول العلاقة بين العمانيين والصينيين في الفترة ما بين القرنين الحادي عشر والخامس عشر - Yingsheng, Liu (مشروع منظمة التربية والثقافة والعلوم "اليونسكو" لدراسة طرق الحرير حصاد الندوة الدولية لطرق الحرير بجامعة السلطان قابوس الفترة من ٢٠ إلى ١١/٢١ سنة ١٩٩٠ م, 1991)

ملخص عام حول اصول الصناعة البحرية على طول ساحل عمان وذلك في عصور ما قبل التاريخ - Cleuziou, Serge (مشروع منظمة التربية والثقافة والعلوم "اليونسكو" لدراسة طرق الحرير حصاد الندوة الدولية لطرق الحرير بجامعة السلطان قابوس الفترة من ٢٠ إلى ١١/٢١ سنة ١٩٩٠ م, 1991)

أثر العصور التاريخية القديمة على الطرق التجارية التى تربط عمان بالعالم الخارجي - السنهورى, الريح (مشروع منظمة التربية والثقافة والعلوم "اليونسكو" لدراسة طرق الحرير حصاد الندوة الدولية لطرق الحرير بجامعة السلطان قابوس الفترة من ٢٠ إلى ١١/٢١ سنة ١٩٩٠ م, 1991)

حضارة بلاد السند وعلاقتها الدكتور التجارية مع عمان في مجال التجارة البحرية - داني, أحمد حسن (مشروع منظمة التربية والثقافة والعلوم "اليونسكو" لدراسة طرق الحرير حصاد الندوة الدولية لطرق الحرير بجامعة السلطان قابوس الفترة من ٢٠ إلى ١١/٢١ سنة ١٩٩٠ م, 1991)

الشواهد الأثرية على وجود التبادل التجاري بين التجار العمانيين من جهة والعالم الخارجي وخاصة الشرق الأقصى من جهة ثانية قبل افتتاح طريق رأس الرجاء الصالح - Costa, Paolo M. (مشروع منظمة التربية والثقافة والعلوم "اليونسكو" لدراسة طرق الحرير حصاد الندوة الدولية لطرق الحرير بجامعة السلطان قابوس الفترة من ٢٠ إلى ١١/٢١ سنة ١٩٩٠ م, 1991)

الدور الذي ساهمت به عمان في طرق الحرير البحرية – العوامل البشرية والتجارية والملاحية التي ساعدت في تحقيق هذا الإنجاز البحري الكبير - Severin, Timothy (مشروع منظمة التربية والثقافة والعلوم "اليونسكو" لدراسة طرق الحرير حصاد الندوة الدولية لطرق الحرير بجامعة السلطان قابوس الفترة من ٢٠ إلى ١١/٢١ سنة ١٩٩٠ م, 1991)
Keywords: Navigation – Oman

مدينة صحار العمانية وعلاقتها بطرق الحرير البحرية - Kervran, Monique (مشروع منظمة التربية والثقافة والعلوم "اليونسكو" لدراسة طرق الحرير حصاد الندوة الدولية لطرق الحرير بجامعة السلطان قابوس الفترة من ٢٠ إلى ١١/٢١ سنة ١٩٩٠ م, 1991)

عمان وطريق تجارة التوابل عبر المحيط الهندي في العصر الاسلام - سالم, سحر السيد عبد العزيز (مشروع منظمة التربية والثقافة والعلوم "اليونسكو" لدراسة طرق الحرير حصاد الندوة الدولية لطرق الحرير بجامعة السلطان قابوس الفترة من ٢٠ إلى ١١/٢١ سنة ١٩٩٠ م, 1991)

اسهام عمان في التواصل الحضاري بين الشعوب - اللواتي, مال الله بن علي بن حبيب (مشروع منظمة التربية والثقافة والعلوم "اليونسكو" لدراسة طرق الحرير حصاد الندوة الدولية لطرق الحرير بجامعة السلطان قابوس الفترة من ٢٠ إلى ١١/٢١ سنة ١٩٩٠ م, 1991)

Medieval Qalhat: Travellers, Dhows and Stone Anchors in South-East Oman - Agius, Dionisius A. (Archaeology of Seafaring: The Indian Ocean in the Ancient Period, 1999)
This study presents the findings of a field trip conducted in 1998 to South-East Oman. The paper firstly looks into the writings of Medieval and Early Modern travellers who visited Qalhat and from their accounts study the types of vessels that were mentioned in connection with the Arabian-Persian Gulf and the Indian Ocean; secondly, to find from the local sailors the types and functions of dhows and what anchors were used for in the recent past. An attempt is made in the present study to reconstruct from the early writings the sea activity and its impact during the time period in question and to establish how much of the information given by the locals of South-East Oman can be corroborated by the findings related to the past.
Keywords: Archéologie – Oman

Rôle des Rostomides dans l'unité du Maghrib des peuples - Fekhar, Brahim Ben Moussa (XIe séminaire sur la Pensée Islamique, 1977)
Keywords: Dynastie rustumide

La sédentarisation autour d’Ouargla - Rouvillois-Brigol, Madeleine (Unesco, 1963)
Keywords: Nomadisme – Ouargla

Political loyalty and the Central Government in pre-colonial Libya - Pennell, C. Richard (Middle East & North African Studies Press (MENAS), 1982)

La politique économique des Kunta au Hoggar au XIX° siècle : la compétition avec le réseau de commerce ibadite pour le contrôle de la saline de l’Amadghor - Belhachemi, Faouzia (Identité, communauté, 1995)
Keywords: Commerce transsaharien

La Libye des origines à 1912 - Mantran, Robert (La Lybie nouvelle : Rupture et continuité, 1975)

Un exil sans royaume: les jeunes juifs du M'zab en Alsace (1962-1982) - Raphaël, Freddy (Les relations intercommunautaires juives en méditerranée occidentale. XIIIe-XXe siècles, 1983)
Keywords: Judaïsme – Mzab

British Aggression Against the Imamate of Oman - Khatib, Fathalla al-; Kabbani, Issam (British imperialism in Southern Arabia, 1958)

Religious Poetry in Early Islam - Gabrieli, Francesco (Arabic poetry: theory and development, 1973)
Keywords: poésie kharijite

Piety and Eschatology in Early Kharijite Poetry - Donner, Fred M. (في محراب المعرفة: دراسات مهداة إلى إحسان عباس, 1997)
Don de l'auteur
Keywords: poésie kharijite

The Mammal Fauna of Oman = الحيوانات البرية في عمان - Harrison, David L. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Faune – Oman

Code Language of Oman = دراسة لرموز اللغات العمانية - Insall, David (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Linguistique – Oman

Dhafari Folklore and Folktale = الفلكلور والروايات الشعبية في ظفار - Johnstone, Thomas Muir (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Littérature – Oman

Traditional Suhari Houses = البيوت التقليدية في صحار - Kervran, Monique (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Architecture – Oman

Some preliminary remarks on a Collection of Poems and Songs of Batahro = دراسة لشعر البطاحرة وأغانيهم - Morris, Miranda (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Poésie – Oman

Arms Manufacture and Arms Trade in South East Arabian in the Early Muslim Era = صناعة وتجارة النحاس في جنوب شرقي الجزيرة العربية في العهد الإسلامي الأول - Nicolle, D. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

Musqut in the Arab Geographers and Lexicographers = مسقط في وجهة نظر الجغرافيين وعلماء اللغة العرب - Smith, G. Rex (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

III mill. Copper in Oman and the Question of Magan = استغلال النحاس في عمان في الألف الثالثة قبل الميلاد - Weisgerber, Gerd (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Archéologie – Oman

أخبار عن عمان في الأدب الجغافي العربي - مارين, مناويلا (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

Some Notes on the Portuguese in Oman = بعض الملاحظات عن البرتغاليين في عمان - Backingham, C. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Relations – Oman – Portugal

New light on the Relationships of Oman and Portuguese (1613-1633) = ملاحطات جديدة عن الصلات بين العمانيين والبرتغاليين - Boxer, C.R. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Relations – Oman – Portugal

The Beduins of Central Oman = بدو عمان الوسطى - Chatty, Dawn (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Nomadisme – Oman

The Project of Khabourah = دراسة ميدانية لمصادر الثروة مشروع الخابورة - Dutton, Roderic (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)

Religious Knowledge in Inner Oman = المعارف الدينية في عمان الداخلية - Eickelman, Dale F. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Enseignement – Oman

The Sinaw Hoard of Early Islamic Coins = خزينة المسكوكات بسيناو من العهد الاسلامي الأول - Lowick, Nicholas (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Numismatique – Oman

Omani Naval Activities of the Southern Arabian Coast in the late 11th/17th Century = النشاط الملاحي العماني على الساحل العربي الجنوبي - Serjeant, Robert Bertram (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Navigation – Oman

Early connection between Oman and East African Coast = التاريخ المبكر لعمان الاسلامية في شرق افريقية - Kirkman, James S. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Relations – Oman – Afrique de l'Est

Fortified Architecture in Oman since 16th century = المباني التاريخية الحربية في عمان منذ القرن السادس عشر - Errico, Enrico d' (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Architecture – Oman

Farming communities in Oman = المجتمعات الزراعية في عمان - Berthoud, T.; Cleuziou, Serge (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Agriculture – Oman

Settlement Patterns in Ancient Oman = دراسة تميدية للاستقرار الحضارى القديم في عمان - Costa, Paolo M. (حصاد ندوة الدراسات العمانية ذوالحجة 1400هـ - نوفمبر 1980م, 1980)
Keywords: Archéologie – Oman

L'île de Djerba - Auxcouteaux de Conty, Henry (Algérie-Tunisie, 1901)
Keywords: Tourisme – Djerba

Le fait berbère et sa lecture coloniale: l'extrême-sud tunisien - Albergoni, Gianni; Pouillon, François (Le mal de voir: ethnologie et orientalisme, politique et épistémologie, critique et autocritique contributions aux colloques Orientalisme, africanisme, américanisme, 9-11 mai 1974, et Ethnologie et politique au Maghreb, 5 juin 1975, 1976)

مصادر ثورة ابي يزيد مخلد ابن كيداد - عباس, إحسان (أشغال المؤتمر الأولتاريخ المغرب العربي و حضارته = Actes du premier congrès d'histoire et de la civilisation du Maghreb, 1979)
Keywords: Ibn Kaydad

Les Juifs du M'zab dans l’Est de la France. Problématique et premières étapes d'une recherche - Raphaël, Freddy (Les relations entre juifs et musulmans en Afrique du Nord: XIX. - XX. sciècles ; actes du colloque international de l'Institut d'Histoire des Pays d'Outres-Mer, Abbaye de Sénanque - octobre 1978, 1980)
Keywords: Judaïsme – Mzab

هامش على مصادر تاريخ الاباضية في المغرب: دراسة لكتاب السير - زغلول, سعد عبد المجيد (أشغال المؤتمر الأولتاريخ المغرب العربي و حضارته = Actes du premier congrès d'histoire et de la civilisation du Maghreb, 1979)
Keywords: Prosopographie – Afrique du Nord

La communauté sépharade de Sarcelles ; une transplantation réussie ? - Vieillard-Baron, Hervé (Formes actuelles de la relocalisation, 1991)
Keywords: Judaïsme – Djerba

The archaeology of Jebel Gharbi (Northwest Libya) and the Libyan sequence - Barich, Barbara E.; Conati Barbaro, Cecilia; Giraudi, Carlo (Interregional Contacts in the Later Prehistory of Northeastem Africa, 1996)
Keywords: Archéologie – Djebel Nefousa

Le M'Zab - Bayyūḍ, Ibrāhim b. ʿUmar (Les Oasis, 1962)
Keywords: Moeurs et coutumes – Mzab

Ouargla et son passé - Ben el Hadj Brahim, Babahamou Azam (Les Oasis, 1962)
Keywords: Sources – Ouargla

Le Mzab d'après les Géographes et les Voyageurs - Huguet, Jacques (XXe congrès national des Sociétés françaises de géographie, 1900)
Keywords: Récits de voyage – Mzab

Ouargla d'aujourd'hui - Herbelin, Jean (Les Oasis, 1962)
Keywords: Moeurs et coutumes – Ouargla

Invitation au M'Zab - Moriaz, Jean (Les Oasis, 1962)
Keywords: Moeurs et coutumes – Mzab

Bassin du versant oriental de la dorsale mozabite - Dubief, Jean (Essai sur l'hydrologie superficielle au Sahara, 1952)
Keywords: Irrigation – Mzab

Ben Youssef Salah - Stora, Benjamin; Ellyas, Akram (Les 100 portes du Maghreb: L'Algérie, le Maroc, la Tunisie, trois voies singulières pour allier islam et modernité, 1999)
Keywords: Ben Youssef; Salah 1907-1961; Biographies

Tadeusz Lewicki (1906-1992) - Bubka, Jolanta; Ostafin, Barbara (Studia Orientalia Thaddaeo Lewicki oblata, 1994)
Keywords: Biographies – Pologne

The Stone Town of Zanzibar - Da Costa, Titus; Meffert, Eric F. (The Architecture of housing: proceedings of an international seminar sponsored by the Aga Khan Award for Architecture, the African Union of Architects, and the Association of Architects of Tanzania, held in Zanzibar, the United Republic of Tanzania, 12-15 October 1988, 1990)
Keywords: Zanzibar

L'itinéraire d'Ibn Battuta en Afrique occidentale au XIVe siècle, les gens de l'or et leur idéologie - Rey, Pierre-Philippe (Terrains et engagements de Claude Meillassoux: hommages, 1998)
Keywords: Commerce transsaharien

La jonction entre réseau Ibadite Berbère et réseau Ibadite Dioula du commerce de l’or, de l’Aïr à Kano et Katsina, au milieu du XVe et la construction de l’empire Songhay par Sonni Ali Ber - Rey, Pierre-Philippe (Au contact Sahara-Sahel. Milieux et sociétés du Niger, 1994)
Keywords: Commerce transsaharien

L'évêque et la cathédrale en Afrique du Nord - Duval, Noël (Actes du XIe congrès international d'archéologie chrétienne, 1989)
Keywords: Christianisme – Afrique du nord

The Ali-Muawiya Conflict and the Kharijite Secession reexamined in the Light of Ibadite Sources - Veccia Vaglieri, Laura (Proceedings of the twenty second Congress of Orientalists: held in Istanbul, September 15th to 22nd, 1951, 1953)
Keywords: Fitnah

Historische Minderheitenforschung am Beispiel einer Neubetrachtung der frühen Ḫariǧitenbewegung – Diskussion eines neuen Forschungsansatzes - Pampus, K.-H. (XIX. Deutscher Orientalistentag : vom 28. September bis 4. Oktober 1975 in Freiburg im Breisgau, 1977)
Keywords: Kharijisme

Pharmacopée traditionnelle saharienne : Sahara septentrional - Maiza, K.; Brac de la Perrière, R.A.; Hammiche, V. (Actes du 2e Colloque Européen d’Ethnopharmacologie et de la 1e Conférence internationale d’Ethnomédecine, Heidelberg, 24-27mars 1993, 1993)
The traditionnaluses of plants for medicine were studied in north algerian Sahara. To date, 85 spontaneousmedicinal plants have been identified, 35 are reported with the vernacularnames and 17s,electedbecause they have common medicinaluse in 3 differentgeographicallocalities and mayserve as an indicator of the major health problems of the populations.
Keywords: Botanique – Mzab

Begadkefat im berberischen - Vycichl, Werner (Hamito-Semitica: proceedings of a colloquium held by the Historical Section of the Linguistics Association, Great Britain at the School of Oriental and African Studies, University of London, on the 18th, 19th and 20th of March 1970, 1975)
Keywords: Linguistique – Djerba

Le rôle du Sahara et les Sahariens dans les relations entre le Nord et le Sud - Lewicki, Tadeusz (Histoire générale de l’Afrique: L’Afrique du VIIe au XIe siècle, 1990)

Les petits états du désert libique et du Sahara tripolitaine dans le Haut Moyen Âge, excepté le Fezzān et le Kaouar - Lewicki, Tadeusz (Atti della Settimana Internazionale di Studi Mediterranei Medioevali e Moderni, Cagliari 1979, 1980)

Quelques observations sur la production poétique des Berbères médiévaux - Lewicki, Tadeusz (Problemy literatur orientalnykh. Materialy II Miedzynarodowego Sympozyum, Warszawa-Kraków 22-26 maja 1972, 1974)
Keywords: Poésie

Ibn al-Ṣaġīr Kronika Tāhertu - Lewicki, Tadeusz (Zrodla Arabskie do Dziejow Slowiansczyny. Tom Drugi Czesc Pierwsza, 1969)
Keywords: Dynastie rustumide

Prophètes antimusulmans chez les Berbères médiévaux - Lewicki, Tadeusz (Atti del Terzo Congresso di Studi arabi e islamici, Ravello 1-6 Settembre 1966, 1967)

Les commerçants ibāḍites nord-africains dans le Soudan au moyen âge - Lewicki, Tadeusz (Trudui dvadtzat’ pyatogo XXV Mezhdunarodnogo Kongressa Vostokovedov, Moskva 19-16 avgusta 1960, 1963)
Keywords: Commerce transsaharien

Foreign relations - Lee-Warner, William (Imperial Gazeteer of India : administrative, 1907)

Les survivances indigènes dans l'onomastique africaine - Frézouls, Edmond (L'Africa romana : atti del VII convegno di studio, Sassari, 15-17 dicembre 1989, 1990)

Dirhams for the Empire - Savage, Elizabeth (Genèse de la ville islamique: en al-Andalus et au Maghreb occidental, 1998)
Keywords: Numismatique

Tunisie - Ben Younes, Habib (La civilisation phénicienne et punique, 1994)
Keywords: Antiquité

Libye - Longerstay, M. (La civilisation phénicienne et punique, 1994)
Keywords: Antiquité

Figure 68. Figure in eastern dress - Baratte, François (From Hannibal to Saint Augustine: ancient art of North Africa from the Musée du Louvre, 1994)
Keywords: Archéologie – Djerba

معتمد الاباضية في الحديث مسند الربيع بن حبيب - دجال, صالح بكير (كتاب الأصالة ، ملتقى السنة النبوية الشريفة : محاضرات و مناقشات ملتقى الفكر الإسلامي السادس عشر 27 - 7 - إلى 03 - 08 - 1982, 1982)
Keywords: Hadith – recueils

La sauvegarde du patrimoine architectural de la vallée du M'zab - Ballalou, Zouhir (La sauvegarde des ensembles historiques urbains en période d'évolution: actes du 1er Colloque international des villes du patrimoine mondial, Québec, Canada, 30 juin au 4 juillet 1991, 1991)
Keywords: Architecture – Mzab

L'enchantement de Djerba - Dumas, Pierre (Arthaud, 1937)
Keywords: Littérature – Djerba

Bagaï, un des châteaux forts du Donatisme - Lamirande, Emilien (Œuvres de Saint Augustin: Traités anti-donatistes, 1965)
On “Breviculus Collationis cum Donatistis”, Collatio tertii diei
Keywords: Donatisme

Les violences des circoncellions d’après le témoignage de saint Augustin - De Veer, Albert C. (Œuvres de Saint Augustin: Traités anti-donatistes, 1968)
On “Contra Cresconium” III
Keywords: Donatisme

Rapport des Donatistes avec les Circoncellions - Lamirande, Emilien (Œuvres de Saint Augustin: Traités anti-donatistes, 1965)
On “Breviculus Collationis cum Donatistis”, Collatio tertii diei
Keywords: Donatisme

“Scelera” et “facinora” au sujet des Circoncelliones - Lamirande, Emilien (Œuvres de Saint Augustin: Traités anti-donatistes, 1965)
On “Breviculus Collationis cum Donatistis”, Collatio tertii diei
Keywords: Donatisme

La population berbère devant les problèmes modernes en Tunisie - Sahli, Sadok (Démographie et destin des sous-populations: colloque de Liège, 21-23 septembre 1981, 1983)
Keywords: Berbérisme – Tunisie

Communal Organization of the Jews of Tripolitania during the Late Ottoman Period - Goldberg, Harvey E. (Jews among Muslims, 1996)
Keywords: Judaïsme – Djebel Nefousa

The Foundations of Kharijite Authority: The Dissemination of Charisma - Dabashi, Hamid (Authority in Islam: From the Rise of Mohammad to the Establishment of the Umayyads, 1989)
Keywords: Kharijisme

‏الاحتلال السقالي لجربة - قوجة, محمد (دراسات حول جزيرة جربة, 1996)
Keywords: Invasions chrétiennes – Djerba

الحملات الاسبانية على جزيرة جربة - القفصي, عبد الكريم (دراسات حول جزيرة جربة, 1996)
Keywords: Invasions chrétiennes – Djerba

Taqdīm Kitāb al-Tuḥaf li-Abī al-Rābīʿ Sulaymān b. Yakhlaf al-Mazātī (471 hijrī/1078 milādī) - Jaʿbīrī, Farḥāt al- (دراسات حول جزيرة جربة, 1996)

‏القيمة الفنية والتاريخية المساجد جربة - المرابط, رياض (دراسات حول جزيرة جربة, 1996)
Keywords: Architecture – Djerba

Baʿḍ al-Mulāḥāḍāt ʿan al-Ḥayāt al-Yawmiyya fī Jazīrat Jarba fī Awākhir al-Ḥarb al-ʿAlāmiyya al-Thāniyya - ʿAnnābī, Ḥasan al- (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Djerba – 1939-1945

al-Jāliyyāt al-Urūbiyya al-Mutawasiṭiyya bi-Jazīrat Jarba (Awāʾil al-Qarn muntaṣaf al-Qarn al-ʿashrīn) - ʿAnnābī, Ḥasan al- (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Emigration – Malte – Djerba

Almānī fī Jarba ḥawl raḥlat al-Mubashir Īfāld - ʿAnnābī, Ḥasan al- (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Récits de voyage – Djerba

Fatrat al-Thalāthināt fī buḥūth al-Bashīr al-Tlīlī - ʿAnnābī, Ḥasan al- (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)

al-Bashīr al-Tlīlī wa nashāṭuhu al-Bīdāghūjī - ʿAyyārī, ʿAlī al- (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)

Usṭūr « al-Gharība » wa Yihūd Jarba ilā al-Ḥarb al-ʿalāmiyya al-Thāniyya - Snoussi, Mohamed Larbi (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Judaïsme – Djerba

Mafhūm al-Wathīqa al-tārīkhiyya - Snoussi, Mohamed Larbi (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Sources

Majmūʿāt al-Jarbiyyīn « al-Shattāt » - Merimi, Mohamed (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Emigration – Djerba – Tunis

في رثاء بشير التليلي - ماجد, جعفر (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Poésie – Djerba

جربة والهجمات الصلبية على افريقية في النصف الأول من القرن الثاني عشر - ممدوح, حسين (دراسات حول جزيرة جربة, 1996)

Aḍwāʾ ʿalā idārat Jarba wajbāytahā min khilāl Qānūn sana 1249-1833 - Ben Tanfous, Aziza (دراسات حول جزيرة جربة, 1996)
Keywords: Taxes – Djerba

Aḍwāʾ ʿalā Idāra Jarba wa wajbāytahā min khilāl al-Qanūn 1249 h. (1830) - Ben Tanfous, Aziza (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)
Keywords: Taxes – Djerba

Les impôts à Jerba au XVIIIe siècle jusqu’à la réforme du décret du XIXe siècle - Ben Tanfous, Aziza (دراسات حول جزيرة جربة, 1996)
Keywords: Taxes – Djerba

Tunisie : hommes et monuments - Ben Tanfous, Aziza (Tunisie : hommes et monuments, 1996)
Keywords: Judaïsme – Djerba

Historical interpretation of the territory of Muscat - Costa, Paolo M. (Oman studies: papers on the archaeology and history of Oman, 1989)
Keywords: Archéologie – Oman

Remarques sur les causes et remède de l'érosion des plages à Djerba - Paskoff, Roland (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie – Djerba; Littoraux – Djerba

An abandoned pottery at Guellala on the Island of Djerba, Tunisia: a hermeneutic approach to ethno archaeology - Johnston, Robert H. (Pots and potters: current approaches in ceramic archaeology, 1984)
Keywords: Archéologie – Djerba

‏الأبعاد الحضرية لجامع أبي مسوار في جزيرة جربة - قوجة, محمد (دراسات حول جزيرة جربة, 1996)
Gouja, Mohamed, 1996, al-Abʿād al-ḥaḍāriyya li-Jāmiʿ Abī Miswār fī Jazīrat Jarba, in: Dirāsāt ḥawl Jazīrat Jarba, Assidje, Houmt-Souk, p. 78-88.
Keywords: Jami al-Kabir; mosquée al- (Hachene; Djerba); Monuments – Djerba; Sidī Yaʿīsh; mosquée (Jaabira; Djerba); Walḥī; mosquée (Oued Zbib; Djerba)

Ṣafāḥāt Khālida min tārīkh Jarba baʿd al-fatḥ al-Islāmī min sana 47 hijrī ilā sana 1298 hijrī - الباروني, سعيد بن يوسف (دراسات حول جزيرة جربة, 1996)
Bārūnī, Saʿīd b. Yūsuf, 1996, Ṣafāḥāt Khālida min tārīkh Jarba baʿd al-fatḥ al-Islāmī min sana 47 hijrī ilā sana 1298 hijrī, in: Dirāsāt ḥawl Jazīrat Jarba, Assidje, Houmt-Souk, p. 120-147.

ʿalāqat Jarba bi-Tārīkh : al-Thābit al-Ijtimāʿī wa’l-imtidād al-Tārīkhī - Jlīdī, ʿAbd al-Qādir al- (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)

Min malāmiḥ al-turāth al-mūsīqī bi-Jazīrat Jarba - Guettat, Mahmoud (Etudes sur l’île de Jerba, 1996)
Keywords: Musique – Djerba

The significance of Khārijism under the ʿAbbāsids - Watt, W. Montgomery (Recherches d'islamologie: recueil d'articles offerts à Georges C. Anawati et Louis Gardet par leurs collègues et amis, 1977)

Iscrizioni augurali a Mascat nel Sultanato dell’Oman - Oman, Giovanni (Studi Arabo-islamici in memoria di Umberto Rizzitano, 1991)
Explanation of two “magical squares” with mysterious letters above the entrance of Bayt al-Falaj, which is a museum these days.

British interests and the use of Indian resources in the Persian Gulf during the Oman revolt (1913-1920) - Prasad, G.D. (Proceedings of the Indian History Congress: fifty-ninth session, Patiala, 1998, 1999)

The limitations of Qur’ānic usage in early Arabic poetry: the example of a Khārijite poem - Qāḍī, Wadād al- (Festschrift Ewald Wagner zum 65. Geburtstag. 2: Studien zur arabischen Dichtung, 1994)
On a poem (a translation is given), a Rā’iyya, by the Khārijite poet ʿAmr b. al-Ḥusayn al-ʿAnbarī (d. after 130/749), composed on the occasion of a battle in Wādī ‘l-Qurā near Mecca, 130/748, in which the Khārijites were routed by an Umayyad army, and in which their leaders, including Abū Ḥamza al-Shārī (Abū Ḥamza al-Mukhtār b. ʿAwf), were killed. See Higgins 2015, who treats the same poem.
Keywords: Abū Ḥamza al-Mukhtār b. ʿAwf; poésie kharijite

Orientamenti nelle ricerche degli Ibāḍiti nell’Africa settentrionale - Rubinacci, Roberto (Universita degli studi di Cagliari. Facolta di Fiurisprundenza e Scienze Politiche. Atti del I Congresso Internazionale di Studi Nord-Africani (Cagliari, 22-25 Gennaio 1965), 1965)
Keywords: Orientalisme – Italie

al-Ṣila bayna ‘l-Muʿtazila wa-Madhhab al-Ibāḍiyya fī Ifrīqiyā al-Shimāliyya - Nallino, Carlo A. (K. al-Turāth al-Yūnānī fī ‘l-Ḥaḍāra al-Islāmiyya. Dirāsāt li-Kibār al-Mustashriqīn., 1940)
[Rapporti fra la dogmatica muʿtazilita e quella degli Ibāḍiti dell’Africa settentrionale]
Keywords: Religions comparées – Ibadisme – Mutazilisme

L’Aqida des Abadhites - Calassanti Motylinski, Adolphe de (Recueil de mémoires et de textes publiés en l’honneur du XIVe Congrès des Orientalistes, 1905)
Text and translation of Muqaddimat al-Tawḥīd (or ʿAqīdat al-ʿAzzāba, or Tawḥīd al-ʿAzzāba) of Abū Ḥafṣ ʿAmr/ʿUmar b. Jamīʿ (508-516 Arabic text; 517-543 translation with annotations; 544-545 a list of Ibāḍī works concerning their ʿAqīda). Pp. 544-545 also in Ould-Braham 2010-2011, 341-342. Lewicki 1936, 275: a sort of catechism in use especially at Jerba. The ʿAqīda was originally in Berber and translated into Arabic by Abū Ḥafṣ ʿUmar b. Jamīʿ (Shammākhī: Siyar, 561-562). L’aquida populaire des abadhites algériens, textes, traductions et notes. Algiers: Fontana, 1905, (43 pp.).
Keywords: Foi – Traité

A proposito dei berberi attuali della Tripolitania - Serra, Luigi (Atti della settimana maghribina: Cagliari 22-25 maggio 1969, 1970)
I.a. the Ibāḍīs of the Tripolitanian peninsula Fārwa are mentioned.
Keywords: Linguistique – Zouara

Ibāḍiyya and orthodox reformism in modern Algeria - Shinar, Pessah (Scripta Hierosolymitana, IX, Studies in Islamic History and Civilization, 1961)
The Ibāḍī establishment in the Mzāb (98). An attempt at Sunnī-Ibāḍī reconciliation (101). Doctrinal similarities (between Reformists and Ibāḍīs) (103). The Mzābī reform movement (107). The Mzābīs and the French (108). The Ibāḍiyya and Arab nationalism (112). The enemy from within (115). On pp. 113-115 Sul. al-Bārūnī and his ideas, on the basis of his writings in the periodical al-Minhāj of Abū Isḥāq Ibr. Iṭfayyish. On pp. 115-119 the ideas of Abū Isḥāq Ibr. Iṭfayyish, on the basis of his writings in his periodical al-Minhāj).
Keywords: Bārūnī; Sulaymān al- (1870-1940); Périodiques – Egypte; Réformisme – Mzab

Sayyid Said, the Imam of Muscat and the development of Zanzibar - Srinivasan, Padma (Proceedings of the Indian History Congress: fifty-ninth session, Patiala, 1998, 1999)
Keywords: Vie politique – Oman – 1804-1856

National awareness, civic rights and the role of the printing press in the 19th century: the careers and opinions of Fāris al-Shidyāq, his colleagues and patrons - Roper, Geoffrey (Democracy in the Middle East : proceedings of the annual conference of the British Society for Middle Eastern Studies, 8-10 July 1992, University of St Andrews, Scotland., 1992)

Ṣuḥār (Sohar) in the early islamic period: the written evidence - Wilkinson, John Craven (South Asian archaeology 1977: papers from the fourth International Conference of the Association of South Asian Archaeologists in Western Europe, held in the Istituto universitario orientale, Naples, 1979)

Democracy in the Islamic world: the agrarian economy as a base for early democratic tendencies in Oman - Ubaydli, Ahmad (Democracy in the Middle East : proceedings of the annual conference of the British Society for Middle Eastern Studies, 8-10 July 1992, University of St Andrews, Scotland., 1992)
Abstract at the beginning of the article: this paper intends to shed light on the agrarian economy in Oman and how it formed a base for democratic tendencies there 132-280/749-893, when the first independent state was established. The Falaj (pl. Aflāj) is an irrigation system where water is carried from source to the user area. Depending on such a system, agriculture in Oman thrived in comparison to the surrounding areas. The way the irrigation system is administered and the relatively ample agricultural products, together with other factors, established a real base for democratic tendencies. Ibāḍism was to a great extent a reflection of such a situation. Chapters on (the administration of) the Aflāj irrigation system, agricultural products, and Ibāḍism.
Keywords: Agriculture – Oman

The independence of the Maghrib - Talbi, Mohamed (General history of Africa: Africa from the Seventh to the Eleventh century, 1988)
Pp. 248-250: Khārijism, a revolutionary doctrine. Pp. 250-252: The Ṣufrite kingdoms. Pp. 252-254: The Ibāḍite kingdoms. Then follow: The decline of Khārijism and the founding of the Idrīsid kingdom; The first attempt at independence in Ifrīqiyā; External relations; Society and culture (Density and variety of population; The social strata; Religious and racial osmosis; Language, arts and sciences; Religious thought).

The role of the Sahara and Saharians in relationships between North and South - Lewicki, Tadeusz (General history of Africa: Africa from the Seventh to the Eleventh century, 1988)
Keywords: Commerce transsaharien

The 1820 expedition to the Gulf and the decline of British commercial shipping: the paradox of the cost of security - Grummon, Stephen R. (Law, personalities, and politics of the Middle East: essays in honor of Majid Khadduri, 1987)

Les liaisons maghrébines sahariennes et soudanaises de la ville de Ouargla au Moyen Āge - Lewicki, Tadeusz (Etudes maghrébines et soudanaises, 1976)
Keywords: Commerce transsaharien

Une commune chrétienne dans l’oasis de Ouargla au Xe siècle - Lewicki, Tadeusz (Etudes maghrébines et soudanaises, 1976)
Keywords: Christianisme – Ouargla

Le monde berbère vu par les écrivains arabes du moyen-âge - Lewicki, Tadeusz (Actes du premier congrès d'études des cultures méditerranéennes d'influence arabo-berbère, 1973)
Especially food and language are being treated. The former treats the food eaten by the nomadic and sedentary people, prohibited food (poultry, eggs, fish) and certain particular practices, e.g. eating dog’s flesh. The latter deals with data on phonetics and grammar, lexical material about the various Berber languages, adaptations of the Arabic alphabet, onomastics, toponymy, etc.
Keywords: Alimentation – Afrique du Nord

Une croyance des Ibāḍites nord-africains sur la fin du monde: le pays de Jughrāf - Lewicki, Tadeusz (Ve Congrès international d'arabisants et d'islamisants: Actes, Bruxelles 31 août-6 septembre 1970, 1970)
The mythical place where all believers, i.e. the Ibāḍīs who preserved their faith, were supposed to gather shortly before the end of times. Lewicki identifies Jughrāf with a valley in the Sahara, called Jughrāf, with a thermal source and palmeries, inhabited by the Tuareg tribe Kel Immidir. In old times, probably already in the 9th century A.D or earlier, a trade route of Ibāḍī merchants leading to Tādmekka and further south to Gao traversed this valley. Later this route fell into disuse and oblivion, and became a semi-mythical symbol. Later Ibāḍī traditionists placed Jughrāf in Oued Righ. Lewicki’s article is mainly based on Warjlānī, Abū Zak. Yaḥyà b. Abī Bakr: K. al-Sīra wa-Akhbār al-A’imma (end of part 2), Anonymous: Siyar al-Mashāyikh, and Shammākhī: K. al-Siyar.

Was Wāṣil a Khārijite? - Watt, W. Montgomery (Islamwissenschaftliche Abhandlungen: Fritz Meier zum sechzigsten Geburtstag, 1974)
P. 311: the conclusion to which this brief study points is that Wāṣil came from what was predominantly a moderate Khārijite background. The doctrine of the Manzila [bayna Manzilatayni] was insufficient in itself to mark him off clearly. He and his followers, though close to the Ibāḍites, seem to have been distinct from them. The probability is that the Muʿtazila were sharply distinguished from the Khārijites only after they had accepted the nickname and given it an honourable meaning by referring it to the five principles. This happened in the ninth century, perhaps in the time of Abū ‘l-Hudhayl, and may be linked with the attempt to claim Wāṣil instead of ʿAmr as forerunner and founder.

Sources for the early history of Oman - Wilkinson, John Craven (Studies in the history of Arabia. Proceedings of the first international symposium on studies in the history of Arabia, 23rd – 28th April 1977, sponsored by the Department of History, Faculty of Arts, University of Riyadh, Saudi-Arabia, 1979)
A very short overview of Omani early history (until the 11th c. A.D.) is followed by a broad outline of sources available, without most of these sources being mentioned in detail, except Sālimī’s Tuḥfat al-Aʿyān.
Keywords: Sources – Oman

Opposing aspects of colonial rule in this century to 1930: the unusual case of the Beni-Mzab - Marks, J. (North Africa: nation, state and religion, 1993)

al-Wujūd al-Burtughālī fī ʿUmān fī ‘l-Maṣādir al-Maḥalliyya al-ʿUmāniyya - Ghannām, Sulaymān Muḥammad al- (Studies in the history of Arabia. Proceedings of the first international symposium on studies in the history of Arabia, 23rd – 28th April 1977, sponsored by the Department of History, Faculty of Arts, University of Riyadh, Saudi-Arabia, 1979)
With regard to the Portuguese presence in Oman, the following sources are mentioned: Ibn Qayṣar: K. Sīrat al-Imām al-ʿĀdil Nāṣir b. Murshid (118-119); Anonymous: Kashf al-Ghumma (119); Ibn Ruzayq: al-Fatḥ al-Mubīn (119); Sālimī: Tuḥfat al-Aʿyān (119-120); Anonymous: [no title]; Anonymous: [no title]. Pp. 121-124: text from Ibn Qayṣar’s work on the period of Imam Nāṣir b. Murshid; p. 124: short text from Kashf al-Ghumma.
Keywords: Relations – Oman – Portugal

La population de la Tunisie vers 1860. Essai d’évaluation d’après les registres fiscaux - Ganiage, Jean (Études maghrébines. Mélanges Charles André Julien, 1964)
Photocopy of pp. 185-186: Jerba.
Keywords: Taxes – Djerba

Being bedouin: nomads and tribes in the Arab social imagination - Eickelman, Dale F. (Changing nomads in a changing world, 1998)
Pp. 41-46 on the MS of Ibr. b. Saʿīd al-ʿIbrī (d. 1975) on the history of the ʿIbriyyūn
Keywords: Nomadisme – Oman

Islam and state expansion in Algeria: nineteenth-century Saharan frontiers - Holsinger, Donald C. (Islamism and secularism in North Africa, 1994)
Keywords: Emigration – Mzab – Algérie

Présence étrangère et exercice du pouvoir politique à Zanzibar, 1840-1873 - Ruphin, Solange-Marie (Histoire africaine du XXe siècle: sociétés, villes, cultures, 1993)
Keywords: Zanzibar

Counting and surveying an « inner » Omani community: Hamra al-ʿAbriyin - Eickelman, Dale F. (Tribe and state: essays in honour of David Montgomery Hart, 1991)

Traditional Islamic learning and the ideas of the person in the twentieth century - Eickelman, Dale F. (Middle Eastern lives: the practice of biography and self-narrative, 1991)
Pp. 48-55 on the MS of Ibr. b. Saʿīd al-ʿIbrī (d. 1975) on the history of the ʿIbriyyūn.

Réseaux d’ulama “swahili” et liens de parenté: une piste de recherche - Kagabo, Jose (Les swahili entre Afrique et Arabie, 1991)
Examination of the biographies of some ʿUlamā’ reveals their tendency to isolate themselves in networks that are very much closed to the original coastal Swahilis, and sometimes without taking into consideration the traditional clivages between Sunnites and Ibadites. Most scholars identify themselves as Arabs and keep the autochtons culturally at a distance. Analysis of the formation of a series of chains of ʿUlamā’ (from the beginning of the 19th century) suggests that the process of education of the ʿUlamā’ is accompanied with great mobility between the centres of religious learning in East Africa (Anjouan, Grand Comores, Lamu, Mombasa, Zanzibar) and in Arabia or Ḥaḍramawt. A great master can claim a long chain of ʿUlamā’ and a great diversity in education. Also kinship relationships play a very important role (Catalogue of the African Studies Centre, Leiden).
Keywords: Zanzibar

Parenté, migrations, alliances: les réseaux omani en Afrique orientale et centrale - Le Cour Grandmaison, Colette (Les swahili entre Afrique et Arabie, 1991)
Departing from precise historical and geographical examples, the author tries to explain the simultaneous or successive articulations between the relationship networks, the alliances and the commercial networks of the sections of the Omani al-Ḥārithī tribe in East and Central Africa. The al-Ḥarithī tribe has some 10.000 members and is composed of 31 sections among which five beduin sections (a list on p. 177). The tribe is characterized by an extreme mobility in space and in time, but despite massive emigration at certain times the tribal structures, apparently, have remained stable.
Keywords: Relations – Oman – Afrique de l'Est

Mosques, merchants and landowners in Zanzibar old stone town - Sheriff, Abdul Mohamed Hussein (Histoire sociale de l'Afrique de l'Est, XIXe-XXe siècle: actes du colloque de Bujumbura, 17-24 octobre 1989, 1991)
Keywords: Zanzibar

Le Kharijisme et la revendication égalitaire des Berbères au Maghreb (VIIIe et IXe siècles) - Djenidi, Abdallah (Dépendance et liberté: l'Afrique et le monde méditerranéen dans l'Antiquité, 1990)

Identité nationale et discours religieux en Oman - Eickelman, Dale F. (Intellectuels et militants de l'Islam contemporain, 1990)
Eickelman discusses religious discours in Oman, starting with a conflict between the Saudi chief Muftī ʿAbd al-ʿAzīz b. Bāz and the Omani chief Muftī Aḥm. b. Ḥamad al-Khalīlī, that started with b. Bāz’s opinion on the Ibāḍī view on the vision of Allāh.
Keywords: Polémique wahhabite

Ibāḍī theological literature - Wilkinson, John Craven (Religion, learning and science in the ʿAbbasid period, 1990)

Le berbère en Tunisie - Boukous, Ahmed (Langue et société au Maghreb: bilan et perspectives, 1989)
An estimated (1952, 1968) 1% of the Tunisian population is Berberophone, of whom 40% are located on the island of Jerba. [In 1989?] at Jerba, Berber speaking people live in Adjim, Guellala, Sadouikech, Elmai, Mahboubine and Sedghiane. Guellala is still completely Berberophone, in Sadouikech half of the population speaks Berber, in Adjim a third, and in Elmai several hundred persons.
Keywords: Linguistique – Djerba

The Omani and Ibāḍī background to the Kilwah Sīrah; the demise of Oman as a political and religious force in the Indian Ocean in the 6th/12th century - Wilkinson, John Craven (A Miscellany of Middle Eastern articles: in memoriam Thomas Muir Johnstone 1924-1983, 1988)
Pp. 131-132: in the MNHC there is an undated MS entitled al-Sīra al-Kilwiyya. This is a composite work made up of the following items: (i) what may be called the Kilwa Sīra proper, that is a piece of rhymed prose called al-Maqāma al-Kilwiyya by Muḥ. b. Saʿīd al-Qalhātī with a commentary by Rāshid b. ʿUmar ... b. al-Naẓar; (ii) Sīra by Abū ‘l-Mundhir Salma b. Muslim al-ʿAwtabī to ʿAlī b. ʿAlī al-Kilwī and his brother al-Ḥasan b. ʿAlī al-Kilwī; (iii) a chapter entitled Bāb fī ‘l-Tawḥīd wa-Tafsīrihi ʿalà Madhhab al-Muslimīn (from a book modelled on K. al-Firdaws) by ʿAbd al-Salām ... Saʿīd b. Aḥm. b. Muḥ. b. Ṣāliḥ; (iv) al-Qaṣīda al-Ḥimyariyya, by Nashwān b. Saʿīd al-Ḥimyarī (d. 573/1178) (see GAL I, 300 (364, ed. 1943) and S I, 527-8). In this article the first two works only will be examined. Discussion will concentrate on the Omani background of these documents, since this contribution is aimed at complementing a study that has been published in the International Journal of African Historical Studies which discusses the implications of these documents for East-African history (Wilkinson 1981).
Keywords: Relations – Oman – Afrique de l'Est

Note sur la transmission des droits d’eau dans les oasis de la Sharqīya - Le Cour Grandmaison, Colette (Hériter en pays musulman: ḥabus, " lait vivant ", manyahuli, 1987)

Yazīd b. Unaisa und Abū ʿĪsà al-Isfahānī: zur Konvergenz zweier sektierischer Bewegungen - Ess, Josef van (Studi in onore di Francesco Gabrieli nel suo ottantesimo compleano, 1984)
Yazīd b. Unaisa was an Ibāḍī who started a sectarian movement predicting a new religion, in which Muslims and Jews, and perhaps also Christians, would be absorbed. Abū ʿĪsà al-Isfahānī was a Jew who started a sectarian movement, in which Muḥammad was recognized as a prophet.

An Arabic source for late Ottoman history - Landau, Jacob M. (Économie et sociétés dans l’empire ottoman (fin du XVIIIe-début du XXe siècle). Actes du Colloque de Strasbourg (1er-5 juillet 1980), 1983)
Arabic text and translation of a trip of al-Sayyid Ḥumūd b. Aḥm. b. Sayf al-Būsaʿīdī (MS in the British Library, MS Or. 8085/25). French abstract on p. 61. A preliminary report on this MS was published in Osmanlı Araştırmaları (Istanbul), I (1980), 133-136. Travel accounts written by local people can constitute important sources for the conditions of life in the Ottoman Empire. Such is the case with the MS Riḥlat al-Sayyid Ḥumūd b. Aḥm. b. Sayf al-Būsaʿīdī, written by an Arab Muslim from Zanzibar. It comprises 42 folios, 16,7x14 cm., 12 lines to each page. The literary Arabic in which the account is written is marred by errors of syntax, accidence and spelling and is interspersed with colloquialisms borrowed from the vernacular of Zanzibar. The author started out from Zanzibar on 26 Shawwāl 1288/8 Jan. 1872. He travelled first to the Ḥijāz to perform the Ḥajj. Then he visited Egypt, Palestine and Syria, reaching as far north as Damascus. Lastly, he returned to Beirut and sailed back to Port Said, where he spent fourteen days waiting for an Ottoman ship to take him home via Suez and Jeddah. Al-Būsaʿīdī is an alert traveller who realistically observes local customs, especially those related to religion. No less relevant, he has noted down a not inconsiderable number of data expressed in facts and figures. He also gives advice on how to travel.
Keywords: Récits de voyage – Zanzibar

Early development of Kalām - Ess, Josef van (Studies on the first century of Islamic society, 1982)

La conversion des Berbères au Khārijisme Ibādito-Sufrite et la nouvelle carte politique du Maghreb au IIe/VIIIe siècle - Talbi, Mohamed (Études d’histoire ifriqiyenne et de civilisation musulmane médiévale, 1982)
In this article, after an explanation of Wilāya - Barā’a, Quʿūd - Khurūj, Shirā’ and Taqiyya/Kitmān in “la théologie politique” of the Khārijites, detailed opinions follow on the introduction of Khārijism in the Maghreb (mainly based on non-Ibāḍī sources; of Ibāḍī sources Le Tourneau 1960, Darjīnī: Ṭabaqāt and Shammākhī: Siyar are mentioned). Treating the introduction of Ibāḍism in the Maghreb, al-Rabīʿ b. Ḥabīb’s Musnad or al-Jāmiʿ al-Ṣaḥīḥ in the redaction of Warjlānī is being discussed (with on page 37 note 2 a discussion of Massignon 1938). Then follow descriptions of the Berber kingdoms of Tāmasna, Tlemcen, the region of Tripoli, Sijilmāsa, Tāhart and Kairouan.

The early development of the Ibāḍi movement in Basra - Wilkinson, John Craven (Studies on the first century of Islamic society, 1982)
The internal view of the development of the Ibāḍī movement (125-126); The Khawārij beginnings (126-131); The Tafrīq of the Khawārij (131-136); The period of “intellectual” development (132-136); Proto-Ibāḍism (136-138); The organization of the Daʿwa (138-140); The Omani conversion (140-143); The Ṣufriyya-Ibāḍiyya split (143-144). At the end of his study, Wilkinson concludes: “So it can be seen that while Ibāḍī doctrine might have originated in a non-tribal milieu, it was closely linked with the political ambitions of tribal or national groups in its period of expansion. At a later stage it was able to modify the excesses of the tribal way of life in Oman, but its history was never divorced wholly from tribal politics. Indeed it could not be, for at root the concepts of the Imāma and Wilāya represented a religious transformation of tribal formulations of political power.”
Keywords: Ibadisme – Irak

Changes in the structure of village life in Oman - Wilkinson, John Craven (Social and economic development in the Arab Gulf, 1980)

The Shiite and Khārijite contribution to pre-Ashʿarite Kalām - Madelung, Wilferd (Islamic philosophical theology, 1979)

Hérésie, acculturation et nationalisme des Berbères barghawāṭa - Talbi, Mohamed (Actes du premier congrès d'études des cultures méditerranéennes d'influence arabo-berbère, 1973)
As far as Ibāḍī sources or secondary literature on al-Ibāḍiyya are concerned, a few references to Marcy 1936. The article starts with an English abstract: the Barghawāṭa were the rulers of a kingdom in Tāmasnā, Morocco (dynasty of Banū Ṭarīf) which lasted for four centuries (124-543/742-1148). Their heretical movement has been regarded by both chroniclers and modern scholars as a gross distortion of Islam. The object of this paper is to put their heretical movement in the perspective of acculturation and nationalism. Such an outlook is allowed by a thorough analysis of the sources of information, leading to the following conclusions: although he may have been of Jewish origin, Ṭarīf embraced the Berber cause under the banner of Ṣufrite Khārijism, at a time when the Berbers were the victim of Arab policy. The Barghawāṭa were not one tribe, but a community of various origins united by a nationalistic feeling. The founder of Barghawāṭism was not Ṣāliḥ b. Ṭarīf, but Yūnus b. Ilyās and his successor Abū Ghufayr. They converted the people through persuasion, providing them with a prophet from among their own people, War-Iyā Warā, and a Koran written in their language, as well as through violence. The author of the article goes on to analyse the unconscious process of formation of Barghawāṭism, as a new ideology emerged through contacts with the East (Yūnus borrowed from Khārijism, Shīʿism and Arab mythology). Acculturation thus assumes the role of a weapon taken from the adversary and used to achieve national liberation.

Kharijitism and the Kharijites - Thomson, William (The Macdonald presentation volume: a tribute to Duncan Black Macdonald, consisting of articles by former students, presented to him on his seventieth birthday, April 9, 1933, 1933)
P. 373: the purpose of this paper is to call attention to some aspects of Khārijite history which have been somewhat neglected, and to propose a change in the point of view from which we at present consider the development of Khārijite doctrines. Briefly stated, the thesis maintained will be that our conception of the origin and nature of Khārijitism require revision, not only in the light of certain historical facts and the known geographical spread of Khārijite sects, but also because the inner relation of Khārijite thought to contemporary movements has not been clearly recognized and its true character defined.
Keywords: Kharijisme

I Berberi tripolitani dal punto di vista politico e sociale - Beguinot, Francesco (Atti del secondo Convegno di Studi Coloniali (Firenze, 12-15 Maggio 1947), 1948)
Keywords: Orientalisme – Italie; Vie intellectuelle – Djebel Nefousa

al-Ibāḍiyya laysū Khawārij - ʿIbrī, Ibrāhīm b. Saʿīd al- (Ajwiba wa-Fatāwà bi-Qalam al-Shaykhayni Ibrāhīm Bayyūḍ al-Jazā’irī wa-Ibrāhīm b. Saʿīd al-ʿIbrī al-ʿUmānī, 1971)
Keywords: Polémique

al-Iḥrām min Jidda. Fatwà... li’l-Ḥujjāj al-Maghāriba - Bayyūḍ, Ibrāhim b. ʿUmar (Ajwiba wa-Fatāwà, 1971)
Keywords: Fiqh – pèlerinages

al-Ibāḍiyya laysū Khawārij - Bayyūḍ, Ibrāhim b. ʿUmar (Ajwiba wa-Fatāwà, 1971)
Keywords: Polémique

al-Mawlid al-Nabawī al-musammà al-Nash’a al-Muḥammadiyya - Ruwāḥī, Nāṣir b. Sālim b. ʿUdayyim al- ([Majmūʿa], 1926)
Recueil factice

al-Niyyāt wa-Alfāẓ al-ʿUqūd wa-mā yujrī Majrāhā - Yaḥmadī, Hilāl b. Zāhir al- ([Majmūʿa], 1925)

Khuṭbatā ‘l-ʿIdayni ‘l-Aḍḥà wa’l-Fiṭr - Kharūṣī, Saʿīd b. Khalfān al- ([Majmūʿa], 1925)
Keywords: Sermons – Oman

Talqīn al-Ṣibyān mā yalzam al-Insān - Sālimī, ʿAbd Allāh b. Ḥumayyid al- ([Majmūʿa], 1925)
Keywords: Enseignement – Oman

Tribe and state: Libyan anomalies - Anderson, Lisa S. (Tribes and state formation in the Middle East, 1990)
Keywords: Vie politique – Djebel Nefousa

Oman - Abdul Karim, Bakri Musa (World survey of Islamic Manuscripts, 1993)
A description (written in 1990) of the situation of the MS collection of Dār al-Makhṭūṭāt wa’l-Wathā’iq (4.500 MSS) and of the private library of al-Sayyid Muḥ. b. Aḥm. al-Būsaʿīdī (established 1986, 2.500 MSS).
Keywords: Manuscrits – Oman

Musnad al-Rabīʿ b. Ḥabīb - Tanūkhī, ʿIzz al-Dīn al- (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Hadith – recueils

Ḥafl fī Mīzāb - Saʿd Allāh, Abū ‘l-Qāsim (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)

Falsafat al-Khawārij - Quṭb, Sayyid (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Kharijisme

al-Ibāḍiyya: al-Madhhab wa’l-Taṣawwur wa’l-Wāqiʿ - Nāṣir, Muḥammad Ṣāliḥ (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)

Khiṭāb Maftūḥ ilà Wazīr al-Shu’ūn al-Dīniyya - Nāṣir, Muḥammad Ṣāliḥ (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)

Makānat al-Ibāḍiyya bayna ‘l-Madhāhib al-Islāmiyya - Muʿammar, ʿAlī Yahyā (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)

al-Ibāḍiyya fī ‘l-Maydān - Majdūb, ʿAbd al-ʿAzīz al- (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)

Madkhal li-Dirāsat al-Dawla al-Rustamiyya wa-Ishāmihā fī ‘l-Taṭawwur al-Fikrī wa’l-Ḥaḍārī - Madanī, Aḥmad Tawfīq al- (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Dynastie rustumide

al-Uṣūl al-Tārīkhiyya li’l-Firqa al-Ibāḍiyya - Khulayfāt, ʿAwaḍ Muḥammad (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)

al-Farq bayna ‘l-Ibāḍiyya wa’l-Khawārij - Iṭfayyish, Abū Isḥāq Ibrāhīm (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Kharijisme

al-Ḥaqq al-Dāmigh: Salāmat al-Manzaʿ; ʿAdm al-Taʿaṣṣub; al-Murūna wa’l-Tasāmuḥ - Khalīlī, Aḥmad b. Ḥamad al- (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Polémique

Barā’at al-Ibāḍiyya - Huwaydī, Fahmī (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)

Risāla ilà al-Shaykh Bayyūḍ ʿan Humūm al-Muslimīn - Fayṣal, Shukrī (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

fī Ḍiyāfat Mīzāb - Bennabi, Malik (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Récits de voyage – Mzab

Dawr al-Madrasa al-Ibāḍiyya fī ‘l-Fiqh wa’l-Ḥaḍāra al-Islāmiyya - Badawī, Ibrāhīm ʿAbd al-ʿAzīz (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Fiqh; Ibadisme – Influence

Hal al-Ibāḍiyya Khawārij? - Bā, ʿUmar b. al-Hājj Muḥammad Ṣālih (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)
Keywords: Kharijisme

al-Ibāḍiyya, Madhhab wa-Sulūk - ʿAbd Rabbih, al-Sayyid ʿAbd al-Ḥāfiz (Makānat al-Ibāḍiyya fī ‘l-Ḥaḍāra al-Islāmiyya, 1992)

al-Mawlid al-Nabawī al-musammà al-Nash’a al-Muḥammadiyya - Ruwāḥī, Nāṣir b. Sālim b. ʿUdayyim al- (Majmūʿ fīhi Muqaddimat al-Tawḥīd; wa-Talqīn al-Ṣibyān; wa-Khuṭbatā al-ʿĪdayni; wa-K. al-Niyyāt; wa’l-Nash’a al-Muḥammadiyya; wa-Qaṣīdat Ghāyat al-Murād fī’l-Tawḥīd; wa-Awʿiya, 1951)
Commissioned by Ḥamūd b. Sālim b. Muḥammad al-Ruwāḥī and his brothers at Zanzibar. 228-235 Fihrist. 227: saḥḥaḥa hādhā ‘l-Kitāb Jamīʿahu wa-iʿtamada Ṭabʿahu Abū Isḥāq Iṭfayyish. Introductions by him on pp. 2-4, 26-38, 177-186.

K. al-Niyyāt wa-Alfāẓ al-ʿUqūd wa-mā yujrī Majrāhā - Yaḥmadī, Hilāl b. Zāhir al- (Majmūʿ fīhi Muqaddimat al-Tawḥīd; wa-Talqīn al-Ṣibyān; wa-Khuṭbatā al-ʿĪdayni; wa-K. al-Niyyāt; wa’l-Nash’a al-Muḥammadiyya; wa-Qaṣīdat Ghāyat al-Murād fī’l-Tawḥīd; wa-Awʿiya, 1951)
Commissioned by Ḥamūd b. Sālim b. Muḥammad al-Ruwāḥī and his brothers at Zanzibar

Khuṭbatā al-ʿĪdayni al-Aḍḥā wa’l-Fiṭr - Khalīlī, Saʿīd b. Khalfān al- (Majmūʿ fīhi Muqaddimat al-Tawḥīd; wa-Talqīn al-Ṣibyān; wa-Khuṭbatā al-ʿĪdayni; wa-K. al-Niyyāt; wa’l-Nash’a al-Muḥammadiyya; wa-Qaṣīdat Ghāyat al-Murād fī’l-Tawḥīd; wa-Awʿiya, 1951)
Commissioned by Ḥamūd b. Sālim b. Muḥammad al-Ruwāḥī and his brothers at Zanzibar

Talqīn al-Ṣibyān mā yalzam al-Insān - Sālimī, ʿAbd Allāh b. Ḥumayyid al- (Majmūʿ fīhi Muqaddimat al-Tawḥīd; wa-Talqīn al-Ṣibyān; wa-Khuṭbatā al-ʿĪdayni; wa-K. al-Niyyāt; wa’l-Nash’a al-Muḥammadiyya; wa-Qaṣīdat Ghāyat al-Murād fī’l-Tawḥīd; wa-Awʿiya, 1951)
Commissioned by Ḥamūd b. Sālim b. Muḥammad al-Ruwāḥī and his brothers at Zanzibar
Keywords: Enseignement – Oman

Ghāyat al-Murād fī ‘l-Iʿtiqād - Sālimī, ʿAbd Allāh b. Ḥumayyid al- (Majmūʿ fīhi Muqaddimat al-Tawḥīd; wa-Talqīn al-Ṣibyān; wa-Khuṭbatā al-ʿĪdayni; wa-K. al-Niyyāt; wa’l-Nash’a al-Muḥammadiyya; wa-Qaṣīdat Ghāyat al-Murād fī’l-Tawḥīd; wa-Awʿiya, 1951)
Commissioned by Ḥamūd b. Sālim b. Muḥammad al-Ruwāḥī and his brothers at Zanzibar

Muqaddimat al-Tawḥīd - Ibn Jamīʿ, Abū Ḥafṣ ʿUmar (Majmūʿ fīhi Muqaddimat al-Tawḥīd; wa-Talqīn al-Ṣibyān; wa-Khuṭbatā al-ʿĪdayni; wa-K. al-Niyyāt; wa’l-Nash’a al-Muḥammadiyya; wa-Qaṣīdat Ghāyat al-Murād fī’l-Tawḥīd; wa-Awʿiya, 1951)
Commissioned by Ḥamūd b. Sālim b. Muḥammad al-Ruwāḥī and his brothers at Zanzibar

al-Binā’ al-Fannī li’l-Qaṣīda fī Shiʿr al-Sayyid Hilāl b. Badr al-Būsaʿīdī - Ḥasan, ʿAbd al-Ḥafīẓ Muḥammad (Qirā’āt fī Fikr al-Sayyid Hilāl b. Badr al-Būsaʿīdī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm al-Sayyid Hilāl b. Badr, al-Fatra 23 Muḥarram 1417/10 June 1996, 1998)
Keywords: Poésie – Oman

al-Ḥass al-Waṭanī wa’l-Jamʿī fī Shiʿr al-Sayyid Hilāl b. Badr al-Būsaʿīdī - ʿAṭāyā, ʿAbd al-Bāsiṭ Saʿīd (Qirā’āt fī Fikr al-Sayyid Hilāl b. Badr al-Būsaʿīdī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm al-Sayyid Hilāl b. Badr, al-Fatra 23 Muḥarram 1417/10 June 1996, 1998)
Keywords: Poésie – Oman

Jawla Taḥlīliyya fī ʿĀlam al-Sayyid Hilāl b. Badr al-Būsaʿīdī - ʿĀnī, Nizār al- (Qirā’āt fī Fikr al-Sayyid Hilāl b. Badr al-Būsaʿīdī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm al-Sayyid Hilāl b. Badr, al-Fatra 23 Muḥarram 1417/10 June 1996, 1998)

Abū Muslim al-Bahlānī al-Ruwāḥī. Ḥayātuhu, Shuyūkhuhu, Talāmīdhuhu, Sulūkiyyātuhu. Al-Madrasa allatī yantamī ilayhā - Siyābī, Aḥmad b. Saʿūd al- (Qirā’āt fī Fikr al-Bahlānī al-Ruwāḥī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī Muslim al-Bahlānī al-Ruwāḥī, 14-16 Rajab 1415/17-19 Dec. 1994, 1998)
Keywords: Biographies – Oman

Abū Muslim al-Bahlānī al-Ruwāḥī fī Shiʿrihi al-Ibtihālī - Nāṣir, Muḥammad Ṣāliḥ (Qirā’āt fī Fikr al-Bahlānī al-Ruwāḥī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī Muslim al-Bahlānī al-Ruwāḥī, 14-16 Rajab 1415/17-19 Dec. 1994, 1998)
Keywords: Poésie – Oman

al-Iṭār al-Mūsīqī li-Shiʿr Abī Muslim al-Bahlānī al-Ruwāḥī - Maḥrūqī, Muḥammad al- (Qirā’āt fī Fikr al-Bahlānī al-Ruwāḥī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī Muslim al-Bahlānī al-Ruwāḥī, 14-16 Rajab 1415/17-19 Dec. 1994, 1998)
Keywords: Poésie – Oman

al-Bahlānī Faqīhan wa-Adīban - Khalīlī, Aḥmad b. Ḥamad al- (Qirā’āt fī Fikr al-Bahlānī al-Ruwāḥī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī Muslim al-Bahlānī al-Ruwāḥī, 14-16 Rajab 1415/17-19 Dec. 1994, 1998)

Bayna Abī Muslim al-Bahlānī al-Ruwāḥī wa-Abī ‘l-Baqā’ al-Randī. Jawānib Adabiyya wa-Fanniyya Muqārana - Haykal, Samīr (Qirā’āt fī Fikr al-Bahlānī al-Ruwāḥī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī Muslim al-Bahlānī al-Ruwāḥī, 14-16 Rajab 1415/17-19 Dec. 1994, 1998)

fī baʿḍ al-Jawānib al-Fanniyya li-Shiʿr Abī Muslim al-Bahlānī al-Ruwāḥī - Darwīsh, Aḥmad (Qirā’āt fī Fikr al-Bahlānī al-Ruwāḥī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī Muslim al-Bahlānī al-Ruwāḥī, 14-16 Rajab 1415/17-19 Dec. 1994, 1998)
Keywords: Poésie – Oman

al-Zaman fī Shiʿr al-Bahlānī al-Ruwāḥī - ʿĀmirī, Hilāl b. Muḥammad al- (Qirā’āt fī Fikr al-Bahlānī al-Ruwāḥī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī Muslim al-Bahlānī al-Ruwāḥī, 14-16 Rajab 1415/17-19 Dec. 1994, 1998)
Keywords: Poésie – Oman

al-ʿAwtabī Mu’arrikhan - Ṭaha, Jād Muḥammad (Qirā’āt fī Fikr al-ʿAwtabī al-Ṣuḥārī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm al-ʿAwtabī al-Ṣuḥārī, al-Fatra min 16-17 Rajab 1416/9-10 Dec. 1995, 1998)

al-ʿAwtabī Nisābatan - Siyābī, Aḥmad b. Saʿūd al- (Qirā’āt fī Fikr al-ʿAwtabī al-Ṣuḥārī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm al-ʿAwtabī al-Ṣuḥārī, al-Fatra min 16-17 Rajab 1416/9-10 Dec. 1995, 1998)

al-Manhaj al-Tārīkhī ʿinda ‘l-ʿAwtabī - Qarqash, Muḥammad (Qirā’āt fī Fikr al-ʿAwtabī al-Ṣuḥārī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm al-ʿAwtabī al-Ṣuḥārī, al-Fatra min 16-17 Rajab 1416/9-10 Dec. 1995, 1998)

al-ʿAwtabī bayna ‘l-Fiqh wa’l-Uṣūl wa’l-Adab - Khalīlī, Aḥmad b. Ḥamad al- (Qirā’āt fī Fikr al-ʿAwtabī al-Ṣuḥārī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm al-ʿAwtabī al-Ṣuḥārī, al-Fatra min 16-17 Rajab 1416/9-10 Dec. 1995, 1998)
Keywords: Fiqh

K. al-Ḍiyā’ (Manhajan, Uslūban, wa-Lughatan) - Ḥasan, ʿAbd al-Ḥafīẓ Muḥammad (Qirā’āt fī Fikr al-ʿAwtabī al-Ṣuḥārī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm al-ʿAwtabī al-Ṣuḥārī, al-Fatra min 16-17 Rajab 1416/9-10 Dec. 1995, 1998)

Muʿjam al-Ibāna li’l-ʿAwtabī. al-Manhaj, al-Lugha, al-Mādda al-Muʿjamiyya, Ṭabīʿtuhā, Maṣādiruhā - Dasūqī, Ibrāhīm al- (Qirā’āt fī Fikr al-ʿAwtabī al-Ṣuḥārī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm al-ʿAwtabī al-Ṣuḥārī, al-Fatra min 16-17 Rajab 1416/9-10 Dec. 1995, 1998)

Qaḍāyā ‘l-ʿAṣr fī Shiʿr Abī ‘l-Ṣūfī - Haykal, Samīr (Qirā’āt fī Fikr Abī ‘l-Ṣūfī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī ‘l-Ṣūfī, al-Fatra 12 Jum. I 1416/7 Oct. 1995, 1998)
Keywords: Poésie – Oman

Ḍarūrāt Abī ‘l-Ṣūfī al-Shiʿriyya. Dirāsa Muqārana - Harūṭ, ʿAlī al- (Qirā’āt fī Fikr Abī ‘l-Ṣūfī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī ‘l-Ṣūfī, al-Fatra 12 Jum. I 1416/7 Oct. 1995, 1998)
Keywords: Poésie – Oman

al-Majāz fī Shiʿr Abī ‘l-Ṣūfī. Dirāsa Dalāliyya - Dasūqī, Ibrāhīm al- (Qirā’āt fī Fikr Abī ‘l-Ṣūfī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī ‘l-Ṣūfī, al-Fatra 12 Jum. I 1416/7 Oct. 1995, 1998)
Keywords: Poésie – Oman

al-Waṣf wa’l-Ṭabīʿa fī Shiʿr Abī ‘l-Ṣūfī - Bāz, al-Saʿīd al- (Qirā’āt fī Fikr Abī ‘l-Ṣūfī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà Iḥtifālan bi-Dhikrà al-Marḥūm Abī ‘l-Ṣūfī, al-Fatra 12 Jum. I 1416/7 Oct. 1995, 1998)
Keywords: Poésie – Oman

Qiṣṣat Alif Rā’ Mīm dhāt al-ʿImād - Bin ʿAlī, Mūsà Bakīr; Bin ʿAlī, ʿAlī Bakīr (Majmūʿ sittat Kutub, 1968)
Completed 21 Jum. I 1323.

Majmūʿ Aḥādīth fī Hawl Yawm al Qiyāma - Bin ʿAlī, Mūsà Bakīr; Bin ʿAlī, ʿAlī Bakīr (Majmūʿ sittat Kutub, 1968)
Completed 21 Jum. I 1323.
Keywords: Hadith – Exégèse

al-Lumʿa al-Murḍiya min Ashiʿʿat al-Ibāḍiyya - Sālimī, ʿAbd Allāh b. Ḥumayyid al- (Majmūʿ sittat Kutub, 1968)
Completed 21 Jum. I 1323.

Kitāb al-Naḥla fī Ghars al-Nakhla - Iṭfayyish, Muḥammad b. Yūsuf (Majmūʿ sittat Kutub, 1968)

Asās al-Ṭāʿāt li-Jamīʿ al-ʿIbādāt - Iṭfayyish, Muḥammad b. Yūsuf (Majmūʿ sittat Kutub, 1968)

Khuṭbat al-ʿĪdayni - Jarbī, Saʿīd b. ʿAlī al- (Majmūʿ sittat Kutub, 1968)

Arab Nationalism and the Idealist Politician : The Career of Sulayman al-Baruni - Peterson, John E. (Law, personalities, and politics of the Middle East: essays in honor of Majid Khadduri, 1987)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

Al-Jānib al-ʿIlmī fī Sharḥ Maqālīd al-Taṣrīf li’l-Khalīlī - Wazīr, Muḥammad al- (Qirā’āt fī Fikr al-Khalīlī. Ḥiṣād al-Nadwa allatī aḥyāhā al-Muntadà Takrīman li’l-Marḥūm al-ʿAllāma al-Muḥaqqiq Saʿīd b. Khalfān al-Khalīlī, 1994)

Al-Shaykh al-ʿAllāma Saʿīd b. Khalfān al-Khalīlī wa-Fikruhu - Rāshidī, Mubārak b. ʿAbdallāh al- (Qirā’āt fī Fikr al-Khalīlī. Ḥiṣād al-Nadwa allatī aḥyāhā al-Muntadà Takrīman li’l-Marḥūm al-ʿAllāma al-Muḥaqqiq Saʿīd b. Khalfān al-Khalīlī, 1994)
Keywords: Biographies – Oman

al-Khalīlī Fiqhiyyan wa-Muḥaqqiqan - Khalīlī, Aḥmad b. Ḥamad al- (Qirā’āt fī Fikr al-Khalīlī. Ḥiṣād al-Nadwa allatī aḥyāhā al-Muntadà Takrīman li’l-Marḥūm al-ʿAllāma al-Muḥaqqiq Saʿīd b. Khalfān al-Khalīlī, 1994)
Keywords: Fiqh

Shāʿiriyyat al-Marḥūm Saʿīd b. Khalfān al-Khalīlī - Ḥasan, ʿAbd al-Ḥafīẓ Muḥammad (Qirā’āt fī Fikr al-Khalīlī. Ḥiṣād al-Nadwa allatī aḥyāhā al-Muntadà Takrīman li’l-Marḥūm al-ʿAllāma al-Muḥaqqiq Saʿīd b. Khalfān al-Khalīlī, 1994)

Maqālīd al-Taṣrīf. Dirāsa Muqārana - Dasūqī, ʿAbd al-ʿAzīz al-Sayyid Ibrāhīm al- (Qirā’āt fī Fikr al-Khalīlī. Ḥiṣād al-Nadwa allatī aḥyāhā al-Muntadà Takrīman li’l-Marḥūm al-ʿAllāma al-Muḥaqqiq Saʿīd b. Khalfān al-Khalīlī, 1994)

al-Shaykh Saʿīd b. Khalfān Balāghiyyan - Bāz, al-Saʿīd al- (Qirā’āt fī Fikr al-Khalīlī. Ḥiṣād al-Nadwa allatī aḥyāhā al-Muntadà Takrīman li’l-Marḥūm al-ʿAllāma al-Muḥaqqiq Saʿīd b. Khalfān al-Khalīlī, 1994)
Keywords: Biographies – Oman

al-Manhaj al-ʿIlmī fī Kitāb Maẓhar al-Khāfī bi-Naẓm al-Kāfī fī ʿIlmay al-ʿArūḍ wa’l-Qawāfī li’l-ʿAllāma al-Muḥaqqiq Saʿīd b. Khalfān al-Khalīlī maʿa Dirāsa ʿArūḍiyya Taṭbīqiyya ʿalà Shiʿrihi - ʿAfīfī, Aḥmad Muṣṭafà (Qirā’āt fī Fikr al-Khalīlī. Ḥiṣād al-Nadwa allatī aḥyāhā al-Muntadà Takrīman li’l-Marḥūm al-ʿAllāma al-Muḥaqqiq Saʿīd b. Khalfān al-Khalīlī, 1994)
Keywords: Poésie – Oman

K. Marāqī ‘l-ʿAwāmm ilà Mabādi’ al-Islām - Ibn Dāwud, Ṣāliḥ b. ʿUmar (Majmūʿat Mutūn Dīniyya. Ta’līf al-Shaykh al-Ḥājj Ṣāliḥ b. ʿUmar wa’l-Shaykh Ibrāhīm b. Abī Bakr., 1966)

Manẓūma fī ‘l-Ḥayḍ wa’l-Nifās wa-Masā’ilihimā - Ibn Abī Bakr, Ibrāhīm (Majmūʿat Mutūn Dīniyya. Ta’līf al-Shaykh al-Ḥājj Ṣāliḥ b. ʿUmar wa’l-Shaykh Ibrāhīm b. Abī Bakr., 1966)
Keywords: Fiqh

Manẓūmat al-Ṣiyām - Ibn Abī Bakr, Ibrāhīm (Majmūʿat Mutūn Dīniyya. Ta’līf al-Shaykh al-Ḥājj Ṣāliḥ b. ʿUmar wa’l-Shaykh Ibrāhīm b. Abī Bakr., 1966)
Keywords: Fiqh – jeûne

Manẓūma. Khulāṣat Marāqī ‘l-ʿAwāmm ilà Mabādi’ al-Islām - Ibn Dāwud, Ṣāliḥ b. ʿUmar (Majmūʿat Mutūn Dīniyya. Ta’līf al-Shaykh al-Ḥājj Ṣāliḥ b. ʿUmar wa’l-Shaykh Ibrāhīm b. Abī Bakr., 1966)

Djerba, centre de diffusion du livre hébraïque - Attal, Robert (Communautés juives des marges sahariennes du Maghreb, 1982)
Keywords: Judaïsme – Djerba

Etre Juif à Djerba - Udovitch, Abraham Labe; Valensi, Lucette (Communautés juives des marges sahariennes du Maghreb, 1982)
Keywords: Judaïsme – Djerba

La mémoire blessée des Juifs du M'zab - Raphaël, Freddy (Communautés juives des marges sahariennes du Maghreb, 1982)
Keywords: Judaïsme – Mzab

Réflexions sur la symbiose judéo-ibadite en Afrique du Nord - Shinar, Pessah (Communautés juives des marges sahariennes du Maghreb, 1982)
A kind of anthropological comparison between Jews and Ibāḍīs in Mīzāb. Shinar concludes: Mīzāb offers us an example of a rare coexistence of two ethnic-socio-cultural isolated groups of people, inequal in numbers and status, which have purely functional contacts. Living closely together, they present notable similarities, but also numerous and profound differences. The Ibāḍīs base their way of life on the Koran, the Tradition, and the Ibāḍī theology, jurisprudence and ethics, with a Berber-Zenati substrate; the Jews base theirs on the Talmudic and mystical biblical tradition, as well as on their ancient Mālikite, especially Moroccon, environment. Both groups, looking outwardly fossilized, have in them the germs of renewal, that orientate the Ibāḍīs towards an oriental renaissance, al-Nahḍa, and the reformism of the orthodox Salafiyya, while the other group, in their exodus, are directed towards Israel and France.
Keywords: Judaïsme – Mzab

La "nation juive" de Ghardaïa - Goutalier, Régine (Communautés juives des marges sahariennes du Maghreb, 1982)
Keywords: Judaïsme – Mzab

Die moderne Entwicklung im nomadisch-bauerlichen Lebensraum der südomanischen Region Dhofar - Janzen, Jörg (Beduinen im Zeichen des Erdöls: Studien zur Entwicklung im beduinischen Lebensraum Südost-Arabiens, 1981)
Keywords: Dhofar

Beduinen in Inner-Oman und ihre “Teilnahme” am gesamtgeschäftlichen Entwicklungsprozess des Sultanats seit der Beginn der Erdölwirtschaft - Scholz, Fred (Beduinen im Zeichen des Erdöls: Studien zur Entwicklung im beduinischen Lebensraum Südost-Arabiens, 1981)
Keywords: Nomadisme – Oman

Moderner Wandel und nomadische Bevölkerungsgruppen in der nordomanischen Küstenebene al-Batinah - Hartmut, Asche (Beduinen im Zeichen des Erdöls: Studien zur Entwicklung im beduinischen Lebensraum Südost-Arabiens, 1981)
Keywords: Nomadisme – Oman

Nomadische/Beduinische Bevölkerungsgruppen als Forschungsproblem und Forschungsgegenstand in der Gegenwart (eine Einführung) - Zimmermann, Wolfgang (Beduinen im Zeichen des Erdöls: Studien zur Entwicklung im beduinischen Lebensraum Südost-Arabiens, 1981)
Keywords: Nomadisme – Oman

Erste Ergebnisse und Tendenzen des jungen Wandels in der Lebens- und Wirtschaftsweise der Nomaden Dhofars/Sultanat Oman - Scholz, Fred (Nomadismus - ein Entwicklungsproblem?, 1982)
Keywords: Dhofar

Entwicklungstendenzen im beduinischen Lebensraum der arabischen Halbinsel unter besonderer Berücksichtigung des Sultanats Oman - Scholz, Fred (Nomadismus - ein Entwicklungsproblem?, 1982)
Keywords: Nomadisme – Oman

Ibadi puritains of Sijilmasa, Rustamid Tahart, and the Libyan Jabal Nafusa - Norris, Harry Thirlwall (The Berbers in Arabic literature, 1982)
Keywords: Sources – Ibadisme

Die Tnuba des Mzab - Suter, Karl (Scritti geografico in onore di Riccardo Riccardi, 1974)
Keywords: Moeurs et coutumes – Mzab

Les Sultans de Kilwa - Ferrand, Gabriel (Mémorial Henri Basset: nouvelles études nord-africaines et orientales, 1928)
Keywords: Zanzibar

Textes berberes en dialecte - Serra, Luigi (Scritti in onore di Laura Veccia Vaglieri, 1964)
Keywords: Linguistique

Les trois jours d'Awussu à Zuara - Paradisi, Umberto (Scritti in onore di Laura Veccia Vaglieri, 1964)
Keywords: Linguistique

The origins of the Omani state - Wilkinson, John Craven (The Arabian peninsula: Society and politics, 1972)

A prevalence of furies: tribes, politics, and religion in Oman and Trucial Oman - Kelly, J.B. (The Arabian peninsula: Society and politics, 1972)
Keywords: Vie politique – Oman – 1932-1970

Maritime trade and Imamate government: two principal themes in the history of Oman to 1728 - Bathurst, Raymond Denis (The Arabian peninsula: Society and politics, 1972)

Military strategy and regional security in the Gulf: the options for the West and the moderate Gulf states - Cordesman, Anthony H. (Oman: economic, social, and strategic developments, 1987)
Keywords: Politique étrangère – Oman – 1970-2020

Oman’s role in the Gulf Cooperation Council and the region - El-Rayyes, Riad N. (Oman: economic, social, and strategic developments, 1987)
Keywords: Politique étrangère – Oman – 1970-2020

Oman, the Gulf and the United States - Anthony, John Duke (Oman: economic, social, and strategic developments, 1987)
Keywords: Relations – Oman – Etats-Unis

Oil in Oman. A short historical note - Hugues, Francis (Oman: economic, social, and strategic developments, 1987)

Successful education and human resource development. The key to sustained economic growth - Birks, J.S.; Sinclair, C. A. (Oman: economic, social, and strategic developments, 1987)

Oman’s development strategy - Whelan, John (Oman: economic, social, and strategic developments, 1987)

Geo-constants in Oman - Bowen-Jones, H. (Oman: economic, social, and strategic developments, 1987)

Updating agriculture and associated rural enterprises - Dutton, Roderic (Oman: economic, social, and strategic developments, 1987)

Indigo. An Arab curiosity and its Omani variations - Balfour-Paul, Jenny (Oman: economic, social, and strategic developments, 1987)

Dhofar. What made it different? - Morris, Miranda (Oman: economic, social, and strategic developments, 1987)
Keywords: Dhofar

Ibadism and the sectarian perpective - Eickelman, Dale F. (Oman: economic, social, and strategic developments, 1987)

Complications of geography, ethnology and tribalism - Barth, Frederik (Oman: economic, social, and strategic developments, 1987)

Oman’s Odyssey: from Imamate to Sultanate - Peterson, John E. (Oman: economic, social, and strategic developments, 1987)
Keywords: Vie politique – Oman – 1970-2020

Changement et continuité en Oman - Wilkinson, John Craven (La Péninsule arabique d'aujourd'hui, 1982)
Keywords: Vie politique – Oman – 1970-2020

L’Oman et l’Afrique Orientale au XIXe siècle - Miège, Jean-Louis (La Péninsule arabique d'aujourd'hui, 1982)
Keywords: Relations – Oman – Afrique de l'Est

La société rurale omanaise - Le Cour Grandmaison, Colette (La Péninsule arabique d'aujourd'hui, 1982)
Keywords: Moeurs et coutumes – Oman

Wathā’iq Jadīda mutaʿalliqa bi-Tārīkh Jazīrat Jarba wa-ʿUlamā’ihā - Qafṣī, ʿAbd al-Ḥakīm al- (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
On some MSS in the Tunisian National Library concerning Jerba around 1510 and the Spanish attack on Jerba in 1560. Furthermore on a MS of Sharḥ K. al-Īsāghūjī by Sul. b. ʿAbd al-Raḥmān al-Maghribī, and another of Sharḥ K. al-Tartīb by Muḥ. b. ʿUmar Abī Sitta al-Sidwīkishī al-Jarbī, and one on Ijāzat ʿAyyād b. ʿUmar b. Qayrāṭ [al-Ṣidghiyānī] al-Jarbī (1838).
Keywords: Manuscrits – Tunis

Wathīqatāni ʿan Tijārat Jarba wa-Ṣfāqis maʿa ‘l-Sharq - Zouari, Ali (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Emigration – Djerba – Egypte

Muqāwamat Jarba li’l-Ghazawāt al-Ūrūbiyya fī ‘l-Qarn al-sādis ʿashar - Būʿazīz, Yaḥyà (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Invasions chrétiennes – Djerba

Abū Ṭāhir Ismāʿīl Mūsà al-Jayṭālī: Ḥayātuhu wa-Ma’āthuruhu - Ibn Marzūq, al-Ṣādiq (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Jayṭālī; Ismāʿīl b. Mūsà (13..-1350)

العلاقات السياسية بين طرابلس وجربة من القرن السادس عشر - الحسناوي, حبيي وداعة (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Relations – Djerba – Djebel Nefousa

Ishāra ilà Ṣāḥib al-Ḥimār fī Rasā’il Ikhwān al-Ṣafā - Marquet, Yves (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Kharijisme

al-Juhūd al-ʿIlmiyya li-ʿUlamā’ Jarba fī Wādī Mīzāb wa-Kubrayāt al-Mudun al-Jazā’iriyya khilāla ‘l-ʿAṣr al-Wasīṭ - Fekhar, Brahim Ben Moussa (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Kharijisme

al-Munāsabāt al-ʿUthmāniyya maʿa Jazīrat Jarba athnā’a Ḥukm Sul. al-Qānūnī - Qarkhān, ʿAbd al-Qādir (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Relations – Djerba – Ottomans

Malāmiḥ ʿan il-Ḥaraka al-ʿIlmiyya ʿinda ‘l-Ibāḍiyya bi-Jarba min al-Fatḥ al-Islāmī Sanat 47 H. ilà Awākhir al-Qarn al-thānī ʿashar Hijrī - Jaabiri, Farhat (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
فرحات بن علي الجعبيري
Keywords: Vie intellectuelle – Djerba – Moyen-âge

Ṣilat Jarba bi-Wād Mzāb - Ibn Yūsuf, Sulaymān Dāwud (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Relations – Djerba – Mzab

al-ʿAlāqa bayna Sukkān Jarba wa-Mzāb - Ṭallāy, Ibrāhīm (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Relations – Djerba – Mzab

ḥawla ‘l-Judhūr al-Ijtimāʿiyya wa’l-Siyāsiyya wa’l-Bashariyya li’l-Firaq al-Ibāḍiyya al-mawjūda bi’l-Janūb al-Tūnisī fī Bidāyat al-ʿAṣr al-Wasīṭ - Ḥasan, Muḥammad (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
On the social, political and tribal factors that influenced the coming into being of the Nukkār, the Khalafiyya and the Naffāthiyya. Ḥasan’s main sources are: Bārūnī: al-Azhār al-Riyāḍiyya; Darjīnī: Ṭabaqāt al-Mashāyikh; Ibn al-Ṣaghīr: Akhbār al-A’imma al-Rustamiyyīn; Shammākhī: K. al-Siyar; Warjlānī: al-Sīra wa-Akhbār al-A’imma. Furthermore: ʿAbd al-Rāziq 1976; Lewicki 1957, 1958, and several of his articles in EI2; Ṭālibī 1978.
Keywords: Nukkarisme

Francesco Domenico Guerrazzi et la bataille de Jerba - Modona, Leo Heppi (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Invasions chrétiennes – Djerba

Quelques épisodes des relations historiques entre l’Espagne et l’île de Djerba - Epalza, Mikel de (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Antiquité; Archéologie – Djerba

Ḥusayn al-Muqaddam, Rā’id min Ruwwād al-Ṣaḥḥāfiyyīn al-Jarbiyyīn bi-Tūnis fī ākhir al-Qarn al-tāsiʿ ʿashar - Sāḥilī, Ḥammādī al- (اعلام من جزيرة جربة, 1996)
Keywords: Journalisme – Djerba

al-Bashīr al-Fūrtī min khilāl Āthārihi - Ibn al-Ḥājj Yaḥyà, al-Jīlānī (اعلام من جزيرة جربة, 1996)
Keywords: Journalisme – Djerba

Mushārakat al-Ustādh Ṣalāḥ al-Dīn al-Tlātlī fī ‘l-Ṣiḥāfa al-Waṭaniyya qabla ‘l-Istiqlāl - Yaʿlawī, Muḥammad al- (اعلام من جزيرة جربة, 1996)
Keywords: Mouvement national – Djerba

al-Bashīr al-Talīlī, Ḥayātuhu wa-Āthāruhu (1935-1986) - Sāḥilī, Ḥammādī al- (اعلام من جزيرة جربة, 1996)
Keywords: Biographies – Djerba – 20e siècle

Muḥammad Badra - Ibn al-Ḥājj Yaḥyà, al-Jīlānī (اعلام من جزيرة جربة, 1996)
Keywords: Biographies – Djerba – 20e siècle

Muḥammad Farīd b. Ghāzī - Farḥāt, al-Munjī (اعلام من جزيرة جربة, 1996)
Keywords: Biographies – Djerba – 20e siècle

Kifāḥ al-Shaykh Sulaymān al-Jāduwī min khilāl Muntakhabāt “Murshid al-Umma” - Yaʿlawī, Muḥammad al- (اعلام من جزيرة جربة, 1996)
Keywords: Journalisme – Djerba; الجادوي، سليمان (1871-1951)

Musāhamat al-Shaykh Sul. al-Jāduwī fī Baʿth al-Ṣiḥāfa al-Hazliyya al-Tūnisiyya min khilāl Jarīdatihi “Abū Nuwās” - Sāḥilī, Ḥammādī al- (اعلام من جزيرة جربة, 1996)
Keywords: Journalisme – Djerba; الجادوي، سليمان (1871-1951)

al-Shaykh Sulaymān al-Jāduwī - Ibn al-Ḥājj Yaḥyà, al-Jīlānī (اعلام من جزيرة جربة, 1996)
Keywords: Journalisme – Djerba; الجادوي، سليمان (1871-1951)

Lamḥa Mūjaza ḥawla Ṣāliḥ Shaybūb al-Jarbī - Qafṣī, ʿAbd al-Ḥakīm al- (اعلام من جزيرة جربة, 1996)
Keywords: Biographies – Djerba – 20e siècle

al-Shaykh ʿAmr b. Jamīʿ, ʿAṣruhu wa-Ḥayātuhu wa-Kitābuhu - Ibn Marzūq, al-Ṣādiq (اعلام من جزيرة جربة, 1996)
Keywords: Biographies – Djerba

أبو الفاضل أبو القاسم بن إبراهيم البرادي - الباروني, سعيد بن يوسف (اعلام من جزيرة جربة, 1996)
Keywords: Barrādī; Abū ‘l-Qāsim b. Ibrāhīm al-; Biographies – Djerba

ابو العباس أحمد الصقلي، قائد بحري من جزيرة جربة - الطيبي, أمين توفيق (اعلام من جزيرة جربة, 1996)
Keywords: Biographies – Djerba

Le périple de P.R.M. Aucher-Eloy dans les montagnes de l’Oman - Ghazanfar, Shahina (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Récits de voyage – Oman

La place du Sultanat dans la vie culturelle française - Chenal, Alain (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Relations – Oman – France

Printemps des relations franco-omanaises sous le règne de Said bin Sultan - Shanfari, Ali Ahmed Bakhit al– (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Relations – Oman – France

La France, l’Oman et l’Océan Indien - Le Cour Grandmaison, Colette (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Relations – Oman – France

L’Oman et la rivalité entre les nations occidentales dans la région de l’Océan Indien - Bhacker, M. Reda (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)

Voyageurs français en Oman - Béguin-Billecocq, Xavier (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Récits de voyage – Oman

Perspectives de coopération entre l’Université Sultan Qaboos et le CNRS - Rowas, Issam al- (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Relations – Oman – France

Boutres francisés de Sour, aspects juridiques - Lafon, Jacques (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Relations – Oman – France

Les relations franco-omanaises et les perspectives d’avenir - Makki, Munir (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Relations – Oman – France

Les premiers consuls de France à Mascate - Berger de Nomazy, Monique (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Relations – Oman – France

Les liens entre l’Oman et la France depuis le XVIIème siècle - Mallalah, Habib (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Relations – Oman – France

L’espace culturel et géostratégique des relations franco-omanaises - Bellec, François (Actes du séminaire France-Oman, aperçus historiques et culturels. Université Sultan Qaboos, 30-31 octobre 1994. Waqā’iʿ Nadwat Lamaḥāt Tārīkhiyya wa-Thaqāfiyya bayna ʿUmān wa-Faransā, 1995)
Keywords: Relations – Oman – France

Juifs maghrébins et commerce transsaharien du VIIIe au XVe siècle - Abitbol, Michel (Le sol, la parole et l'écrit: 2000 ans d'histoire africaine, 1981)
Keywords: Judaïsme – Djerba

العلاقات بين جزيرتي جربة وصقليّة في أواخر القرون الوسطى (1100-1500) - الطيبي, أمين توفيق (دراسات حول جزيرة جربة, 1996)
Al-Ṭībī, Amīn, 1996, al-ʿalāqāt bayn jazīrat Jarba wa Ṣaqaliyya fī Awākhir al-Qurūn al-Wasīṭī (1100-1500 milādī), in: Dirāsāt ḥawl Jazirat Jarba, Assidje, Houmt-Souk, p. 7-33.
Keywords: Relations – Djerba – Sicile

Sauvegarde du patrimoine architectural de l'île de Djerba: Contribution à la discussion - Hayder, Wolf (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Sauvegarde du patrimoine architectural et naturel face au développement - Gazzola, Piero (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Conclusions et recommandations de la commission sur les édifices - Fendri, Mohamed (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Jerba - Centre des arts et traditions populaires (Les Costumes traditionnels féminins de Tunisie, 1972)
Midoun Mahboubine : Tenue de sortie en été Futa Domyati Midoun Mahboubine : tenue de sortie en hiver Tunsi Guellala : costume de jelwa : qmejja Ajim : drapé de mariage Houmt-Souk : costume de mariée le jour de jelwa : futa el barat Hara Kbira : costue de mariée des femmes juives : izâr
Keywords: Artisanat – Djerba

Jerba, une ile de la Méditerranée face aux problèmes du développement - Bouabid, Moncef (L’Homme méditerranéen et la mer. Actes du IIIe Congrès International d’Etudes des Cultures de la Méditerranée Occidentale (Jerba, avril 1981), 1985)
Keywords: Urbanisme – Djerba

Conclusions et recommandations de la commission sur les structures urbaines - Bouabid, Moncef (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Urbanisme – Djerba

Pour un développement de Djerba qui tienne compte de son équilibre écologique - Calpini, Gustavo (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

La Ghriba: rendez-vous séculaire sur l’île de Jerba - Freund, Wolfgang Slim (Kunst, Kommunikation, Kultur: Festschrift zum 80. Geburtstag von Alphons Silbermann, 1989)
Keywords: Judaïsme – Djerba

Gaṣr al-ḥāğ, un grenier fortifié dans la djeffara libyenne - Ayoub, Abderrahman; Quellec, Jean-Loïc Le (Les Techniques de conservation des grains à long terme : leur rôle dans la dynamique des systèmes de cultures et des sociétés, 1981)
Keywords: Economie domestique – Djebel Nefousa

دور المرأة في الحركة العلمية بجبل نفوسة من القرن الثالث إلى القرن السادس الهجريين / 9 - 12 م قراءة أولية لمخطوط آباضي من قرن 6 هـ / 12 م - بوبة, مجاني (أعمال ندوة: تاريخ النساء المغاربيات: الإقصاء وردات الفعل, 1997)

Die Insel Djerba. Wachstumsprobleme und Wandlungsprozesse eines südtunesischen Kulturraumes - Klug, Heinz (Kulturgeographische Untersuchungen im islamischen Orient, 1973)
Keywords: Agriculture – Djerba

Évolution du peuplement et de l’habitat djerbiens - Tlatli, Salah-Eddine (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Urbanisme – Djerba

Jerba : espace insulaire, développement touristique et comportement humain - Chapoutot, Jean Mohamed Mehdi (Le tourisme au Maghreb: diversification du produit et développement local et régional, 1999)
Keywords: Tourisme – Djerba

Les mouvements migratoires et leurs effets sur l’île de Jerba - Kassah, Abdelfattah (Migrations internationales entre le Maghreb et l'Europe: les effets sur les pays de destination et d'origine, 1999)
Keywords: Démographie – Djerba

Aspects géographiques et démographiques de l’île de Djerba - Mzabi, Hassouna (Histoire préislamique de Djerba, 1979)
Keywords: Démographie – Djerba

Djerba et les îles de la Méditerranée à travers quelques écrits de Béchir Tlili : Djerba et la Corse - Tlili-Sellaouti, Rachida (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)

Djerba, île de douceur et d'harmonie - Combès, Jean-Louis (Dans la lumière des cités africaines, 1956)

Béchir Tlili et la recherche historique - El Ghoul, Fayçal (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)

Der westliche Teil (Algerische Region) - Suter, Karl (Die Sahara und ihre Randgebiete, 1972)
Keywords: Géographie – Mzab

Qatāda b. Diʿāma as-Sadūsī et la science du ḥadīṯ - Vitestam, Gösta (Actes du 5è Congrès International d'Arabisants et d'Islamisants : Bruxelles 31 Août - 6 Septembre 1970., 1970)
Keywords: Hadith – Exégèse – Irak

The Ibāḍis - Rubinacci, Roberto (Religion in the Middle East: three religions in concord and conflict, 1981)

Jerba et le monde méditerranéen au Moyen Âge - Mansouri, Mohamed Tahar (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)

Bibliographie sur l’île de Djerba - Assidje (Étude commune sur les paysages littoraux, 1979)
Keywords: Bibliographie – Djerba

Utilisation de l’espace à Djerba - Yamoun, Messaoud (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Urbanisme – Djerba

Contribution aux études d’aménagement de Midoun, Houmt Souk et de leur région - Bonacorsi, G.E. (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Urbanisme – Djerba

Aspects géographiques et démographiques de Djerba - Direction de l'aménagement et du territoire (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Démographie – Djerba

Depuis le Séminaire - El Cadi, Férid (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Djerba, structuration urbaine - Djelassi, Fethi (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Urbanisme – Djerba

Caractéristiques de l’habitat et évolution de l’urbanisation - Direction de l'aménagement et du territoire (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba; Urbanisme – Djerba

The Concept of Authority in Islamic Thought: lā ḥukma illā lillāh - Arkoun, Mohammed (The Islamic world from classical to modern times: essays in honor of Bernard Lewis, 1989)

«Hérétiques de toutes les religions, unissez-vous !» - Rougemont, D. de (Mélanges offerts à Henry Corbin, 1977)

Y a-t-il une influence khârigite dans la pensée d'Ibn Tûmart ? - Ben Hamadi, Amor (Mélanges offerts à Mohamed Talbi à l'occasion de son 70e anniversaire, 1993)
Keywords: Kharijisme

Et Ben Youssef signa son arrêt de mort - Bessis, Juliette (Dossiers secrets du Maghreb et du Moyen-Orient . - 4. 1992, 1992)
Keywords: Ben Youssef; Salah 1907-1961

L’impact de la colonisation sur les échanges à Jerba - Ben Hamida, Abdessalem (Colloque d’histoire Béchir Tlili. Etudes sur l’Histoire de Jerba. Actes des rencontres du colloque (1988, 1990, 1992, 1994), 1996)

La Fabbricazione degli isnād nella scuola ibāḍita: il Musnad di ar-Rabīʿ b. Ḥabīb - Francesca, Ersilia (Law, Christianity and modernism in Islamic society: proceedings of the Eighteenth Congress of the Union Européenne des Arabisants et Islamisants, held at the Katholieke Universiteit Leuven (September 3-September 9, 1996), 1998)
A detailed study of al-Rabīʿ b. Ḥabīb’s sources. On pp. 54-56 a brief description of the development of Ibāḍī jurisprudence between the 1st/7th and 3rd/9th centuries.
Keywords: Hadith – Exégèse

La pêche et ses techniques sur les côtes de l'Africa - Trousset, Pol (Méditerranée antique : pêche, navigation, commerce : [actes des Congrès nationaux des sociétés historiques et scientifiques, Section d'archéologie et d'histoire de l'art] : [120e, Aix-en-Provence, 23-29 octobre 1995 et 121e, Nice, 26-31 octobre 1996], 1998)
Keywords: Pêche – Djerba

Schiiten und Charidschiten - Strothmann, Rudolph (Religionsgeschichte des Orients in der Zeit der Weltreligionen, 1961)
Keywords: Kharijisme

Le catholicisme des Européens de l’Île de Jerba (Tunisie) dans les années 1840 à 1880 - Soumille, Paul (Iles de Méditerranée: actes de la Table ronde du Groupement d'intérêt scientifique Sciences humaines sur l'aire méditerranéenne, Aix-en-Provence, octobre 1980, 1981)
Keywords: Christianisme – Djerba

Annexe de Djerba (Nomenclature et répartition des tribus de Tunisie, 1900)
Keywords: Communes – Djerba

Le Bordj Ghazi Mustapha - Gharib, Rachid (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Chronique d'Ibn Saghir sur les Imams Rostemides de Tahert - Calassanti Motylinski, Adolphe de (Actes du XIVe Congrès international des orientalistes, 1908)
Keywords: Dynastie rustumide

Le manuscrit arabo-berbère de Zouagha découvert par M. Rebillet. Notice sommaire et extraits - Calassanti Motylinski, Adolphe de (Actes du XIVe Congrès international des orientalistes, 1908)
Deals with a MS of Ibn Ghānim’s Mudawwana, which is in Berber and in Arabic with a Berber commentary. Photos in the possession of Rebillet. After a short introduction, Motylinski gives short extracts in French, Arabic and Berber (pp. 71-78). The dates at the end of the parts of the MS are 1288/1872-3, 1289 and 1290.
Through www.eboxeditions.com, the following title is available (Aug. 2012): al-Mudawwana al-Kubrà li-Ibn Ghānim/Moudawana d’Ibn Ghanim. Berbère-arabe. Nuṣūṣ muqtabasa bi’l-ʿArabiyya wa’l-Amāzīghiyya. Extraits de passages manuscrits. Commentés en français par Adolphe de Calassanti Motylinski. This document begins with Motylinski 1907, here in 11 pp., followed by 122 pp. in the handwriting of Motylinski, from al-Mudawwana.*
Keywords: Fiqh – Libye – 8e siècle; Linguistique – Djebel Nefousa

Expédition de Pedro de Navarre et de Garcia de Tolède contre Djerba (1510) d’après les sources abadhites - Calassanti Motylinski, Adolphe de (Actes du XIVe Congrès international des orientalistes, 1908)
Arabic text (pp. 134-143) and translation (pp. 144-159). The author of the MS is unknown. P. 134: Hādhā Tārīkh li-baʿḍ Aṣḥābinā ... Tārīkh Istīlā’ al-Naṣārà -dammarahum Allāh- ʿalà Madīnat Wahrān -khallaṣahā Allāh- wa-Akhdhihim baʿdahā Madīnat Bujāya wa-Madīnat Ṭarāblus -aʿādahumā Allāh ilà ‘l-Islām- wa-Wurūdihim ilà Jazīrat Jarba .... P. 142: Dhikr Wurūdihim ... li-Balad Sfāqiṣ wa-Nuzūlihim bi-Jazīrat Qarqanna. Monchicourt 1913, 69 note 1: the text is the same as the part on this campaign in Bossoutrot 1903, but it is not treated as succinctly (5 pp. in Motylinski). Motylinski had already indicated this text in Motylinski 1885a, 71-72.
Keywords: Invasions chrétiennes – Djerba

Die Belagerung von Djerba im Jahre 1560: zu einer Zeichnung in der Königlichen Bibliothek, Stockholm - Ehrensvärd, Ulla (Turcica et Orientalia: Studies in Honor of Gunnar Jarring on his Eightieth Birthday, 12 October 1987, 1988)
Keywords: Invasions chrétiennes – Djerba – 1560

Documents musulmans pour servir à une histoire de Djerba - Bossoutrot, Jean-Auguste (Jerba une île méditerranéenne dans l’Histoire. Recueil de notes, articles et rapport anciens, 1982)

En Tunisie, le golfe de Gabes 1888 - Servonnet, Jean; Lafitte (Jerba une île méditerranéenne dans l’Histoire. Recueil de notes, articles et rapport anciens, 1982)
Keywords: Monuments – Djerba; Récits de voyage – Djerba; Sidi Garus; mosquée (Haddada; Djerba); Sidi Jmur; mosquée (El Groo; Djerba)

Rapport de Jacob Hartmayer à Monsieur le Ministre Résident Général de France à Tunis (15 mars 1887) - Hartmayer, Jacob (Jerba une île méditerranéenne dans l’Histoire. Recueil de notes, articles et rapport anciens, 1982)
Keywords: Contrôleurs civils – Djerba

Monographie de l’île de Djerba - Brulard, Armand (Jerba une île méditerranéenne dans l’Histoire. Recueil de notes, articles et rapport anciens, 1982)
Keywords: Monuments – Djerba; Récits de voyage – Djerba; Sidi Abd Allah; mosquée (Mezrane; Djerba); Sidi Jmur; mosquée (El Groo; Djerba); Tâjdît; Mosquée (Fâtû; Djerba)

Géographie comparée de la province romaine d’Afrique (1884) - Tissot, Charles (Jerba une île méditerranéenne dans l’Histoire. Recueil de notes, articles et rapport anciens, 1982)
Keywords: Djerba – Province romaine d'Afrique

Chronik des Edlen en Ramon Muntaner. Traduction de J. A. C. Buchon : Chroniques étrangères relatives aux expéditions françaises pendant le XIIIème s. de Ramon Muntaner. - Lanz, Karl F. W. (Jerba une île méditerranéenne dans l’Histoire. Recueil de notes, articles et rapport anciens, 1982)
Keywords: Muntaner; Ramón (1265-1336)

Djerba à la période des Zirides - Golvin, Lucien (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Relations – Djerba – Zirides

Les relations commerciales entre Djerba et la République de Venise à la fin du Moyen-Âge - Doumerc, Bernard (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Relations – Djerba – Italie

L’île de Djerba de la conquête musulmane à la conquête almohade - Bourouiba, Rachid (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Invasion arabe – Djerba

Jerba et la mer - Yamoun, Messaoud (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Pêche – Djerba

L’évolution récente de l’île de Djerba - Sari, Djilali (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Urbanisme – Djerba

Considérations sur l’importance stratégique de Jerba entre 1881 et 1918 - Sainte-Marie, Alain (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Djerba – 1881-1956

Les rivalités Franco-Italienne à Jerba au lendemain de l’établissement du Protectorat Français en Tunisie - El Ghoul, Ferid (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Djerba – 1881-1956

Jerba, Bou-Grara et la question du commerce transsaharien, à la fin du XIXe Siècle - ʿAnnābī, Ḥasan al- (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Commerce transsaharien

La situation économique et sociale à Djerba pendant le premier quart de siècle du Protectorat (1881-1906) d’après trois rapports du Cpt Hartmayer - Ben Hamida, Abdessalem (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Contrôleurs civils – Djerba

Quelques considérations sur l’oeuvre d’Alfonso d’Ulloa “La historia de l’impresa de Tripoli di Barberia” - Valabrega, Guido (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Invasions chrétiennes – Djerba; Invasions chrétiennes – Tripoli

Un Voyageur Français à Jerba en 1708 - Lebrun, François (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Récits de voyage – Djerba

La défaite de la flotte espagnole à Jerba en 1510 dans le Diari de Marin Sanudo et dans les Lettres de Battistello de Tonsis - Galletti, Mirella (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Invasions chrétiennes – Djerba

Un manuscrit ibadite de Jerba les Aqual Quatada - Ess, Josef van (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Fiqh – Ibadisme

Malta and Djerba, 1241-1798 - Wettinger, Godfrey (Liber amicorum: essays on art, history, cartography and bibliography in honour of Dr Albert Ganado, 1994)
Keywords: Relations – Djerba – Malte

Rabai and Zanzibar - Reed, Colin (Pastors, Partners and Paternalists: African Church Leaders and Western Missionaries in the Anglican Church in Kenya, 1850-1900, 1997)
Keywords: Zanzibar

The Tripoli Republic, 1918-1922 - Anderson, Lisa S. (Social & Economic Development of Libya, 1982)
Keywords: Bārūnī; Sulaymān al- (1870-1940); al-Ǧumhūriyyaẗ al-Ṭarābulusiyya (1918-1922)

Migration interne et classes moyennes en Algérie : le cas des Mozabites - Holsinger, Donald C. (Les Classes moyennes au Maghreb: ouvrage collectif, 1980)
Keywords: Emigration – Mzab – Algérie

100 jeux traditionnels du sud de la Tunisie - Ayoub, Abderrahman (Jeu et sports en Méditerranée: actes du Colloque de Carthage 7-8-9 novembre 1989, 1991)
Keywords: Jeux – Djerba

La découverte de Sedrata - Berchem, Marguerite van (Proceedings of the twenty-second Congress of Orientalists, held in Istanbul, September 15th to 22nd, 1951., 1951)
Keywords: Archéologie – Sedrata

À la recherche de Sedrata - Berchem, Marguerite van (Archaeologica orientalia in memoriam Ernst Herzfeld., 1952)
Keywords: Archéologie – Sedrata

Le palais de Sedrata dans le désert saharien - Berchem, Marguerite van (Studies in Islamic art and architecture in honour of Professor K.A.C. Creswell., 1965)
Keywords: Archéologie – Sedrata

Quelques remarques sur le développement de l'île de Djerba et les problèmes qui se posent pour la conservation de son patrimoine architectural - Ben Baaziz, Sadok (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Les plans d'aménagement touristiques : principes directeurs - Barbouch, Abdellatif (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

L’organisation traditionnelle à Djerba - Ben Salem, Cherif; Ben Ayed (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Un militant du réformisme et de la modernisation Ibrahim Bayyoudh - Djeghloul, Abdelkader (Eléments d'histoire culturelle algérienne, 1984)
Keywords: Bayyūḍ; Ibrāhīm ibn ʿUmar (1899-1981); Réformisme – Mzab

Grandeur et limites du refus culturel. Mohamed Atfiyach (1818-1914) - Djeghloul, Abdelkader (Eléments d'histoire culturelle algérienne, 1984)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914)

Pour la sauvegarde du patrimoine et de l'environnement d'une île méditerranéenne: L'Ile de Djerba, Tunisie - Mimita, Mohamed Ajmi (Old cultures in new worlds. 8th ICOMOS General Assembly and International Symposium. Programme report - Compte rendu, 1987)
Djerba has some lI1onuments with a modest size but very a rich architecture: mosques, houses or Menzels, fondouks, pottery and weaving workshops souks that constitute the strong and sublime expression of an art of a popular tradition and they retrace the main lines of the history of the island frOM the oldest ages till nowadays. It is to be regretted that for modernisM sake all these monuments are disappearing or they are damaged in a vertiginous way by nature and mainly by man.
Keywords: Architecture – Djerba

Le rôle des associations du patrimoine - El Cadi, Férid (Actes de la Rencontre "Musées, civilisation et développement": Amman, Jordanie, 26-30 avril 1994 = Proceedings of the Encounter "Museums, Civilization, and Development": Amman, Jordan, 26-30 April 1994, 1994)
Keywords: Architecture – Djerba

Su due poemetti berberi ibāḍiti (note preliminari) - Serra, Luigi (Gli interscambi culturali e socio-economici fra l'Africa settentrionale e l'Europa mediterranea: Atti del Congresso Internazionale di Amalfi, 1983, 1986)
Keywords: Linguistique – Djebel Nefousa; Poésie – Djebel Nefousa

Djerba, l'île de l'étrangère - Kateb, Yacine (Hanîn Prosa aus dem Maghreb, 1989)
Keywords: Littérature – Djerba

Social and political structures in the Jafara plain in the late nineteenth century - Joffé, E. George H.; McLachlan, Keith Stanley (Social & Economic Development of Libya, 1982)

The significance of the occurrence of Abu Ghaylan and Kiklah Formations east of Wadi Ghan, eastern Jabal Nfusah - Fatmi, A. N.; Sbeta, Ali (The geology of Libya. Volume VI. Third Symposium on the Geology of Libya, held at Tripoli, September 27-30, 1987, 1991)
Major and trace element data of Jabal Nafusah phonolites are compared with those of other phonolitic provinces: Rhoen, Hegau and Kaiserstuhl (West Germany); Massif Central and Velay (France); and - with data from the literature - Kenyites and other phonolites of Kenya. In this geochemical comparison the character of the Jabal Nafusah phonolites can be specified exactly. Additional new analytical data are given for the elements Nb, U, Th, F, S and Cl. Between Zr, Nb, U and Th there are positive correlations. Plots of Rb versus Nb, and particularly Nb versus Zr reveal "fans", illustrating the individual differentiation trends of the distinct phonolite provinces. A plot on hyperbolic axes brings the data of the diverging fan to a common curve. Each province occupies its own field on this diagram; the Jabal Nafusah phonolites are situated in an extreme position. On triangular plots it can be shown that the Jabal Nafusah phonolites are enriched (relative to other elements) in Al, Na, Fe, Ca, K, Ti, Zr, F, Cl and Th as compared with other phonolitic provinces; but depleted in Mg, S, Nb and P.
Keywords: Géologie – Djebel Nefousa

Depositional environments of the Chicla, Cabao and Chameau Mort Formations as revealed by scanning electron microcopy - El-Zouki, A. Y. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie – Djebel Nefousa

Water resources of the Socialist People's Libyan Arab Jamahiriya - Pallas, D. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie – Djebel Nefousa

Structural control of groundwater flow in the Mesozoic sandstone aquifers of the eastern part of Jabal Nafusah, Libya. - Singh, G. D. S. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie – Djebel Nefousa

Stratigraphy and lithofacies of the continental clastics (Upper Jurassic and Lower Cretaceous) of Jabal Nafusah, NW Libya. - El-Zouki, A. Y. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie – Djebel Nefousa

Stratigraphic nomenclature of the pre-Upper Cretaceous Mesozoic rocks of Jabal Nafusah, NW Libya. - Fatmi, A. N.; Eliagoubi, B. A.; Hammuda, O. S. (The geology of Libya. Volume I. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978., 1980)
Keywords: Géologie – Djebel Nefousa

Some geochemical aspects of Al Aziziyah Formation, Jabal Nafusah - Ben Ashour, A. M.; Zaied, A.; Bakush, M. (The geology of Libya. Third Symposium on the Geology of Libya, held at Tripoli, September 27-30, 1987, 1991)
Keywords: Géologie – Djebel Nefousa

Geochemical position of the Jabal Nafusah phonolites - Bausch, W. M.; Meduna, J. U. (The geology of Libya. Volume VI. Third Symposium on the Geology of Libya, held at Tripoli, September 27-30, 1987, 1991)
Major and trace element data of Jabal Nafusah phonolites are compared with those of other phonolitic provinces: Rhoen, Hegau and Kaiserstuhl (West Germany); Massif Central and Velay (France); and - with data from the literature - Kenyites and other phonolites of Kenya. In this geochemical comparison the character of the Jabal Nafusah phonolites can be specified exactly. Additional new analytical data are given for the elements Nb, U, Th, F, S and Cl. Between Zr, Nb, U and Th there are positive correlations. Plots of Rb versus Nb, and particularly Nb versus Zr reveal "fans", illustrating the individual differentiation trends of the distinct phonolite provinces. A plot on hyperbolic axes brings the data of the diverging fan to a common curve. Each province occupies its own field on this diagram; the Jabal Nafusah phonolites are situated in an extreme position. On triangular plots it can be shown that the Jabal Nafusah phonolites are enriched (relative to other elements) in Al, Na, Fe, Ca, K, Ti, Zr, F, Cl and Th as compared with other phonolitic provinces; but depleted in Mg, S, Nb and P.
Keywords: Géologie – Djebel Nefousa

A propos de la mer et de la fête d’Awussu chez une population berbère: notes d’information - Serra, Luigi (L’Homme méditerranéen et la mer. Actes du IIIe Congrès International d’Etudes des Cultures de la Méditerranée Occidentale (Jerba, avril 1981), 1985)
Keywords: Coutumes – Zouara

Le Lexique commun aux dialectes berbères orientaux - Serra, Luigi (Actes du deuxième Congrès international d'études des cultures de la Méditerranée occidentale, 1978)
Keywords: Linguistique – Djebel Nefousa

Le Vocabulaire berbère de la mer - Serra, Luigi (Actes du premier congrès d'études des cultures méditerranéennes d'influence arabo-berbère, 1973)
Keywords: Linguistique – Zouara

Sul possessivo nel dialetto berbero di Zuara (Tripolitania) - Serra, Luigi (A la croisée des études libyco-berbères: mélanges offerts à Paulette Galand-Pernet et Lionel Galand, 1993)
Keywords: Linguistique – Zouara

Some properties of Zuara nouns with special reference to those with consonant initial - Mitchell, Terence Frederic (Mémorial André Basset: 1895-1956, 1957)
Keywords: Linguistique – Djebel Nefousa

Long consonants in Phonology and Phonetics - Mitchell, Terence Frederic (Studies in linguistic analysis. special issue of the Philological Society, 1957)
Keywords: Linguistique – Djebel Nefousa

Les monnaies de Tahert aux VIIIe et XIXe siècles - Eustache, Daniel (Le département de Tiaret, 1962)
Keywords: Numismatique – Tahert

Les Rostémides, peuple démocratique et austère - Gharbi, Hadj-Mekki (Le département de Tiaret, 1962)
Keywords: Dynastie rustumide

Djerba, l’île de l’étrangère, Parmi les herbes qui refleurissent, Le Bain des maudits - Kateb, Yacine (L'oeuvre en fragments: inédits littéraires et textes retrouvés, 1986)
Keywords: Littérature – Djerba

Le vocabulaire maritime arabe du Golfe de Gabès et berbère de l’île de Jerba - Louis, André (III Congresso Internazionale di Studi Linguistici Mediterranei (31-5 avril 1969), 1969)
Keywords: Linguistique

Problèmes de la sauvegarde de l’architecture et de l’environnement - Abderrezek, Lotfi (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Pour une approche de la maison djerbienne - Miletti, Gian Carlo (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Analyse de l’architecture traditionnelle à Djerba - Mimita, Mohamed Ajmi (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Sauver Djerba - Mimita, Mohamed Ajmi (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

L'évolution du mouvement international de sauvegarde du patrimoine traditionnel - Miotto, Luciana (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Aspects de l’architecture traditionnelle de Djerba - Hantous, Tahar; El Younsi, Salah (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba; Bûlaymân; Mosquée (Ja’bîra; Djerba); Monuments – Djerba; Tîfarrûjîn; mosquée (Oualagh; Djerba)

Ouargla - Rouvillois-Brigol, Madeleine (Oasis du Sahara algérien. Etudes de photo-interprétation, 1973)
Keywords: Géographie – Ouargla

Le théâtre de rue - Ben Aïssa, Slimane (Algérie, des voix dans la tourmente: témoignages de 40 écrivains, artistes, et hommes politiques algériens, 1999)
Keywords: Théâtre – Mzab

Mozabites - Benyoucef, Brahim (Algérie, des voix dans la tourmente: témoignages de 40 écrivains, artistes, et hommes politiques algériens, 1999)

Les espaces religieux au Mzab - Hadj Nacer, Brahim (Espaces maghrébins: pratiques et enjeux, 1989)

La langue berbère : entre marginalisation et affirmation - Chaker, Salem (Langues du Maghreb et du Sud méditerranéen, 1999)
Keywords: Linguistique

Leçon donnée par un chacal à un saint - Basset, René (Mille et un contes, récits & légendes arabes. Légendes religieuses, 1926)
Keywords: Littérature

Principes et concepts de la démarche patrimoniale - Boumaza, Nadir (1996)
Keywords: Architecture – Mzab; Urbanisme – Mzab

A woman without her distaff : gender, works, and handicraft production in colonial North Africa - Clancy-Smith, Julia (Social history of women and gender in the modern Middle East, 1999)
Keywords: Artisanat – Djerba; Artisanat – Mzab

Permanence de rites traditionnels dans les cérémonies du mariage tunisien aujourd’hui - Louis, André (Al-Bahit : Festschrift Joseph Henninger : zum 70. Geburtstag am 12. Mai 1976, 1976)
Keywords: Moeurs et coutumes – Djerba

Aspects du patrimoine musical de l’île de Jerba - Guettat, Mahmoud (Etudes sur l’île de Jerba, 1996)
Keywords: Musique – Djerba

Culture and Politics in a Village of Immigrants from Djerba - Deshen, Shlomo; Jaeger, D. (Rural Settlements of New Immigrants in Israel, 1971)
Keywords: Judaïsme – Djerba

Piyyut melodies as Mirrors of Social Change in Djerba, Tunisia - Davis, Ruth Frances (From Iberia to diaspora: studies in Sephardic history and culture, 1999)
Keywords: Judaïsme – Djerba

Songs of the Jews on the Island of Djerba - Davis, Ruth Frances (Joodse Cultuur, 1998)
Keywords: Judaïsme – Djerba

Les réinvestissements en Tunisie des revenus des commerçants du Sud Tunisien en France - Boubakri, Hassan (Les effets des migrations internationales sur les pays d’origine : le cas du Maghreb, 1990)
Keywords: Emigration – Djerba – France

Les Plages de la Tunisie: études sur leur évolution - Paskoff, Roland (Editec, 1985)
Un Espace cotier à protéger : la fleche littorale de Ras Rmel à Djerba L’érosion des plages dans le Sud tunisien: exemples a Djerba (cotes Est et Sud-Est) et à Zarzis
Keywords: Géologie – Djerba

Les sédiments du littoral et leur mobilité : Introduction à l'étude des mécanismes sédimentaires - Le Nindre, Y. M.; Howa, H. (Éditions BRGM, 1999)
Keywords: Littoraux – Djerba

Etude paléo-écologique (pollen et macrorestes) d’un dépôt tourbeux dans l'île de Djerba, Tunisie méridionale - Damblon, Freddy; Vanden Berghen, Constant (Biogéographie et palynologie, 1991)
Keywords: Botanique – Djerba

Conclusions et recommandations de la commission sur la géographie, l’écologie et l’économie - Buchmann, Ernst (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Recherches sur les berbérophones, Djerba, Hoggar, Maroc - Benoit, Fernand; Kossovitch, N. (XVe Congrès International d'Anthropologie & d'Archéologie Préhistorique 20-27 septembre 1931, 1933)
Keywords: Biologie – Djerba

L'artisanat de la poterie en Tunisie - Sethom, Hafedh (Imprimerie nationale, 1964)
p. 528-527: Les villages d’artisans-potiers de l’île de Djerba
Keywords: Artisanat – Djerba

Les bijoux de djerba - Gargouri-Sethom, Samira (دراسات حول جزيرة جربة, 1996)
Keywords: Artisanat – Djerba

The Mzab - Alport, E. A. (Arabs and Berbers: from tribe to nation in North Africa, 1973)
Keywords: Ibadisme – Algérie

Histoire préislamique de Djerba. Tableau chronologique - Quoniam, Pierre (Etudes sur l’île de Jerba, 1996)
Keywords: Archéologie – Djerba; Lîmis; mosquée (Ajim; Djerba); Monuments – Djerba

Meninx, terre des Lotophages - Quoniam, Pierre (Histoire préislamique de Djerba, 1979)
Keywords: Archéologie – Djerba

Île de Djerba - Godin (Enquête sur les installations hydrauliques romaines en Tunisie, 1904)
Keywords: Archéologie – Djerba

Du lac Triton des Anciens au projet de mer saharienne, histoire d’une utopie - Trousset, Pol (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Antiquité; Archéologie – Djerba

Le site d’el Kantara (Meninx ?) à Jerba, remarque sur le décor architectonique - Ferchiou, Naïdé (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Antiquité; Archéologie – Djerba

La frontière de la Tingitane - Rébuffat, René (Frontières et limites géographiques de l'Afrique du Nord antique : Hommage à Pierre Salama, 1999)
Keywords: Antiquité; Archéologie – Djerba

L’habitat traditionnel: un problème d'avenir: essai de réaménagement de certains menzels et de leur intégration dans la vie contemporaine - Akkari-Weriemmi, Jenina (Séminaire pour la sauvegarde de l’architecture et de l’environnement de Djerba (23-26 janvier 1975) Communications et recommandations, 1975)
Keywords: Architecture – Djerba

Reconnaissances archéologiques et découverte d’un Mausolée Lybico-Punique à Henchir Bourgou près de Midoun - Akkari-Weriemmi, Jenina (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Antiquité; Archéologie – Djerba; Bourgou; Henchir (Midoun; Djerba); Monuments – Djerba

La guerilla libyenne 1911-1932. Impérialisme et résistance antin-coloniale en Afrique du Nord dans les années 1920 - Davico, Rosalba (Abd El-Krim et la République du Rif, 1976)
Keywords: Bārūnī; Sulaymān al- (1870-1940); Invasion italienne – Libye

al-Shaykh Saʿīd b. Taʿārīt wa fikruhu al-islāmī - Ibn Taʿārīt, ʿAlī (اعلام من جزيرة جربة, 1996)
Keywords: Biographies – Djerba

René Stablo, contrôleur civil à Djerba 1936-1941 - Ben Tahar, Jamel (Les relations tuniso-françaises au miroir des élites, Actes du colloque organisé à la Faculté des Lettres - Manouba les 2 et 3 décembre 1994, 1997)
Keywords: Contrôleurs civils – Djerba